Composition, magnetic particle-containing film, and electronic component
A composition with FE atoms and rheology control agents enhances acid resistance and sedimentation stability in magnetic particle-containing films, addressing peeling issues and ensuring the performance of electronic components.
Patent Information
- Application Number
- JP2022550584
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-18
- Filing Date
- 2021-09-15
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2041-09-15
AI Technical Summary
Existing compositions containing magnetic particles for electronic circuits face issues with acid resistance and sedimentation stability, leading to potential peeling of layers during manufacturing processes.
A composition comprising 70 to 90% FE atoms with a crystal structure, average particle size of 2 to 30 μm, aspect ratio less than 8, and the inclusion of a rheology control agent, along with specific polymer compounds, is used to form a magnetic particle-containing film with enhanced acid resistance and sedimentation stability.
The composition achieves improved magnetic permeability, acid resistance, and sedimentation stability, ensuring the integrity and performance of electronic components.
Smart Images

Figure 0007627280000001 
Figure 0007627280000002 
Figure 0007627280000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition, a magnetic particle-containing film, and an electronic component. [Background technology]
[0002] As electronic devices become more compact and powerful, the integration of electronic circuits is increasing. Coating-type compositions containing magnetic particles are one of the materials that can improve integration. By using such compositions, magnetic bodies can be mounted in any shape, making it easier to realize smaller electronic devices with higher performance than the conventional method of placing individual pieces of magnetic bodies on a chip.
[0003] Coating compositions containing magnetic particles and films formed from the compositions are required to have various durability properties since they are exposed to the manufacturing process of electronic circuits. For example, Patent Document 1 describes a process for producing a resin sheet having a support, the resin sheet including a support and a resin composition layer provided on the support, on an inner layer substrate such that the resin composition layer is bonded to the inner layer substrate, (B) a step of thermally curing the resin composition layer to form an insulating layer; (C) drilling holes in the insulating layer; (D) performing a wet desmear treatment on the surface of the insulating layer using an oxidizing agent solution; and (E) forming a conductor layer on the surface of the insulating layer that has been subjected to the wet desmear treatment; A method for manufacturing an inductor substrate, in which an inductor is formed by a plurality of insulating layers and a plurality of conductor layers, comprising the steps of: The resin composition layer is formed from a resin composition containing a magnetic filler, "A method for manufacturing an inductor substrate, in which the weight loss rate of the magnetic filler is 0% or more and 40% or less when the magnetic filler is kept in an acidic solution of pH 1 at 20°C for 3 hours." (See claim 1) Specifically, Patent Document 1 uses a magnetic filler having magnetic powder and a coating layer that coats the magnetic powder (hereinafter also referred to as "coated magnetic particles") to suppress "a decrease in peel strength between the insulating layer and the conductor layer" that can occur in the process of performing a wet desmear treatment using an oxidizing agent solution. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-067960 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors have prepared and examined coated magnetic particles and compositions containing the coated magnetic particles with reference to the Examples section of Patent Document 1, and have found that the acid resistance of a film formed from the composition may not meet the current standards. They have also found that as the dispersion of the coated magnetic particles progresses during the dispersion treatment, peeling of the coating layer from the magnetic powder may occur.
[0006] Incidentally, a magnetic film is required to have excellent magnetic permeability as a basic performance. In addition, in the case of a coating-type composition containing magnetic particles, the composition is required to have excellent basic performance in that the magnetic particles are stably dispersed in the composition even after long-term aging (hereinafter, also referred to as "sedimentation stability").
[0007] Therefore, an object of the present invention is to provide a composition capable of forming a magnetic particle-containing film having excellent magnetic permeability and acid resistance, and having excellent sedimentation stability. Another object of the present invention is to provide a magnetic particle-containing film related to the composition, and an electronic component including the magnetic particle-containing film. [Means for solving the problem]
[0008] The present inventors have found that the above problems can be solved by the following configuration.
[0009] [1] Magnetic particles containing 70 to 90 mass % Fe atoms, having an Fe crystal structure, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; and a rheology control agent. [2] Magnetic particles containing 70 to 90 mass % Fe atoms, having a half-width of a diffraction peak appearing in the range of 2θ of 42 to 48° of 0.2 to 3° in an X-ray diffraction pattern obtained by an X-ray diffraction method, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; and a rheology control agent. [3] The composition according to [1], wherein the magnetic particles have a half-value width of a diffraction peak appearing in a 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by X-ray diffractometry of 0.2 to 3°. [4] The composition according to any one of [1] to [3], wherein the content of the magnetic particles is 70 to 90 mass % based on the total mass of the composition. [5] The composition according to any one of [1] to [4], wherein the rheology control agent is at least one selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes. [6] The composition according to any one of [1] to [5], further comprising a curing component that is cured by light or heat. [7] The composition according to [6], wherein the curing component includes a polymerizable compound. [8] The composition according to [7], wherein the polymerizable compound includes a compound containing at least one of an epoxy group and an oxetanyl group. [9] The composition according to any one of [1] to [8], further comprising a polymerization initiator.
[10] The composition is substantially free of a solvent, or The composition according to any one of [1] to [9], wherein the composition further comprises a solvent, and the content of the solvent is 1 mass % or more and less than 12 mass % with respect to the total mass of the composition.
[11] A magnetic particle-containing film formed using the composition according to any one of [1] to
[10] .
[12] An electronic component comprising the magnetic particle-containing film according to
[11] .
[13] The electronic component according to
[12] , which is used as an inductor.
[14] The electronic component according to
[12] , which is used as an antenna. Effect of the Invention
[0010] According to the present invention, it is possible to provide a composition capable of forming a magnetic particle-containing film having excellent magnetic permeability and acid resistance, and having excellent sedimentation stability. In addition, according to the present invention, it is possible to provide a magnetic particle-containing film relating to the above composition, and an electronic component including the magnetic particle-containing film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In the present specification, the notation of groups (atomic groups) that does not indicate whether they are substituted or unsubstituted includes both unsubstituted and substituted groups, unless it is contrary to the spirit of the present invention. For example, an "alkyl group" includes not only an alkyl group that does not have a substituent (unsubstituted alkyl group), but also an alkyl group that has a substituent (substituted alkyl group). In addition, an "organic group" in the present specification refers to a group that contains at least one carbon atom.
[0012] In this specification, "actinic rays" or "radiation" refers to, for example, the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light (EUV light: extreme ultraviolet), X-rays, and electron beams (EB), etc. In this specification, "light" refers to actinic rays or radiation. In this specification, unless otherwise specified, "exposure" includes not only exposure to the emission spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light, X-rays, EUV light, and the like, but also drawing with particle beams such as electron beams and ion beams.
[0013] In this specification, the symbol "to" is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0014] In this specification, (meth)acrylate refers to acrylate and methacrylate, (meth)acrylic refers to acrylic and methacrylic, and (meth)acryloyl refers to acryloyl and methacryloyl.
[0015] In this specification, the "solid content" of a composition means the components that form a magnetic particle-containing film, and when the composition contains a solvent (organic solvent, water, etc.), it means all components excluding the solvent. In addition, liquid components are also considered to be solid contents as long as they form a magnetic particle-containing film.
[0016] In this specification, the weight average molecular weight (Mw) is a value calculated as polystyrene by the GPC (Gel Permeation Chromatography) method. In this specification, the GPC method is based on a method using HLC-8020GPC (manufactured by Tosoh Corporation), TSKgel SuperHZM-H, TSKgel SuperHZ4000, and TSKgel SuperHZ2000 (manufactured by Tosoh Corporation, 4.6 mm ID x 15 cm) as columns, and THF (tetrahydrofuran) as an eluent.
[0017] In addition, in this specification, unless otherwise specified, each component may be used alone or in combination of two or more substances corresponding to each component. Here, when two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified.
[0018] [Composition] The composition of the present invention (hereinafter sometimes referred to as "Composition A") contains magnetic particles (hereinafter sometimes referred to as "specific magnetic particles") which contain 70 to 90 mass% Fe atoms, have an Fe crystal structure (hereinafter sometimes abbreviated as "crystal structure"), have an average particle size of 2 to 30 μm and an aspect ratio of less than 8, and a rheology control agent.
[0019] Among ferromagnetic metals, magnetic particles containing Fe atoms (hereinafter also referred to as "Fe atom-containing magnetic particles") exhibit high magnetic permeability, but on the other hand, because of their large negative standard oxidation-reduction potential (i.e., large ionization tendency), they are easily dissolved in acid when immersed in an acidic solution. In other words, there are concerns that magnetic particle-containing films containing Fe atom-containing magnetic particles have excellent magnetic permeability but poor acid resistance. Note that the greater the content of Fe atom-containing magnetic particles in the magnetic particles, the higher the magnetic permeability of the magnetic particle-containing film that is formed, but it is thought that the film is more easily dissolved in acid, and therefore its acid resistance is deteriorated. In response to this, the present inventors have found through their current investigations that when the Fe atom-containing magnetic particles have a crystalline structure, the acid resistance of the magnetic particle-containing film formed is significantly improved (the reason for this is that, since the Fe atom-containing magnetic particles have a crystalline structure, they are less likely to be oxidized and their original composition is less likely to change even when immersed in an acidic solution, and therefore it is assumed that this results in less deterioration of magnetic permeability and excellent acid resistance). In particular, it has been found that when the Fe atom-containing magnetic particles have a crystalline structure and the Fe atom content is 70 to 90 mass%, the magnetic particle-containing film formed can achieve both high magnetic permeability and excellent acid resistance. The present inventors have further investigated based on the above findings and have found that the above-mentioned composition of the present invention can solve the problem of the invention. The details of why the composition having such a composition can solve the problem of the invention are not clear, but it is roughly presumed as follows.
[0020] As described above, when the specific magnetic particles have a crystal structure and the Fe atom content is 70 to 90 mass %, the magnetic particle-containing film formed can have both high magnetic permeability and excellent acid resistance. In addition, by making the aspect ratio of the specific magnetic particles less than 8, the magnetic particles are easily arranged isotropically in the magnetic particle-containing film, which is presumed to contribute to the improvement of the magnetic permeability of the magnetic particle-containing film formed. On the other hand, magnetic particles having an aspect ratio of less than 8 tend to settle in the composition more easily than magnetic particles having an aspect ratio of 8 or more, and tend to adversely affect the sedimentation stability. For this reason, in the composition of the present invention, the average particle size of the specific magnetic particles is set to 2 to 30 μm, and a rheology control agent is introduced into the composition to ensure the sedimentation stability. It is presumed that the dispersibility of the specific magnetic particles is improved by introducing a rheology control agent into the composition, and as a result, the magnetic particles are more uniformly arranged in the magnetic particle-containing film. It is also presumed that this contributes to the improvement of the magnetic permeability of the magnetic particle-containing film formed.
[0021] Hereinafter, the effect of the present invention will be referred to as being superior when at least one of the sedimentation stability of the composition, the magnetic permeability of the magnetic particle-containing film formed, and the acid resistance of the magnetic particle-containing film formed is superior.
[0022] First, the various components contained in the composition will be described below.
[0023] [Magnetic particles] <Specific magnetic particles> The composition includes specific magnetic particles. The specific magnetic particles are magnetic particles that contain 70-90% by mass of Fe atoms, have an Fe crystal structure, have an average particle size of 2-30 μm, and have an aspect ratio of less than 8.
[0024] The specific magnetic particles contain iron atoms (Fe atoms) as metal atoms. The iron atoms may be contained in the magnetic particles as an alloy containing iron atoms (preferably a magnetic alloy containing iron atoms), an iron oxide (preferably a magnetic iron oxide), an iron nitride (preferably a magnetic iron nitride), or an iron carbide (preferably a magnetic iron carbide). The iron atom content is 70-90% by mass relative to the total mass of the specific magnetic particles. When the iron atom content is 70% by mass or more relative to the total mass of the specific magnetic particles, the magnetic particle-containing film formed has excellent magnetic permeability. When the iron atom content is 90% by mass or less relative to the total mass of the specific magnetic particles, the magnetic particle-containing film formed has excellent acid resistance. The lower limit of the iron atom content is preferably 75% by mass or more, more preferably 80% by mass or more, based on the total mass of the specific magnetic particles, and the upper limit of the iron atom content is preferably 88% by mass or less, based on the total mass of the specific magnetic particles.
[0025] The specific magnetic particles may contain metal atoms other than iron atoms. The "other metal atoms" referred to here also include metalloid atoms such as boron, silicon, germanium, arsenic, antimony, and tellurium. The other metal atoms may be included in the magnetic particles as an alloy (preferably a magnetic alloy), a metal oxide (preferably a magnetic oxide), a metal nitride (preferably a magnetic nitride), or a metal carbide (preferably a magnetic carbide) containing the metal atoms.
[0026] The lower limit of the content of metal atoms (total content of iron atoms and other metal atoms) in the specific magnetic particles is 70% by mass or more, preferably 75% by mass or more, more preferably 80% by mass or more, based on the total mass of the specific magnetic particles. The upper limit of the content of metal atoms (iron atoms and other metal atoms) is preferably 100% by mass or less, more preferably 90% by mass or less, based on the total mass of the specific magnetic particles.
[0027] In addition, examples of materials other than iron atoms that constitute the specific magnetic particles include Ni, Co, Al, Si, S, Sc, Ti, V, Cu, Y, Mo, Rh, Pd, Ag, Sn, Sb, Te, Ba, Ta, W, Re, Au, Bi, La, Ce, Pr, Nd, P, Zn, Sr, Zr, Mn, Cr, Nb, Pb, Ca, B, C, N, and O. The specific magnetic particles preferably contain one or more atoms selected from the group consisting of Si, Cr, C, P, Cu, Nb, and B as materials other than iron atoms.
[0028] When the specific magnetic particles contain Cu atoms, the content of Cu atoms is preferably 0.1 to 10 mass %, more preferably 0.1 to 5 mass %, and even more preferably 0.1 to 3 mass %, relative to the total mass of the specific magnetic particles.
[0029] When the specific magnetic particles contain Nb atoms, the content of Nb atoms is preferably 2 to 10 mass %, more preferably 3 to 8 mass %, and even more preferably 4 to 6 mass %, relative to the total mass of the specific magnetic particles.
[0030] When the specific magnetic particles contain B atoms, the content of B atoms is preferably 1 to 4 mass %, and more preferably 2 to 4 mass %, based on the total mass of the specific magnetic particles.
[0031] When the specific magnetic particles contain Si atoms, the content of Si atoms is preferably 1 to 20 mass %, more preferably 3 to 15 mass %, and even more preferably 5 to 10 mass %, relative to the total mass of the specific magnetic particles.
[0032] When the specific magnetic particles contain Cr atoms, the content of Cr atoms is preferably 0.001 to 1 mass %, more preferably 0.005 to 0.5 mass %, and even more preferably 0.01 to 0.1 mass %, relative to the total mass of the specific magnetic particles.
[0033] When the specific magnetic particles contain C atoms, the content of C atoms is preferably 0.001 to 1 mass %, more preferably 0.005 to 0.5 mass %, and even more preferably 0.01 to 0.2 mass %, relative to the total mass of the specific magnetic particles.
[0034] When the specific magnetic particles contain P atoms, the content of P atoms is preferably 0.001 to 10 mass %, more preferably 0.01 to 10 mass %, and even more preferably 0.1 to 10 mass %, relative to the total mass of the specific magnetic particles.
[0035] The content of each metal atom in a specific magnetic particle can be identified by high-frequency inductively coupled plasma (ICP) emission spectrometry.
[0036] The specific magnetic particles have an Fe crystal structure (crystal structure). The presence or absence of a crystalline structure and its properties can be identified by X-ray diffraction measurements and electron microscopes (e.g., transmission electron microscopes (TEM)). The type of crystal structure that the specific magnetic particles have can be, for example, an α-Fe crystal phase. When the specific magnetic particles have the above-mentioned crystal structure, a peak can be observed, for example, at a diffraction angle (2θ) of 42 to 48° in an X-ray diffraction pattern obtained by X-ray diffraction using the 2θ method. In other words, when the specific magnetic particles have the above-mentioned crystal structure, the specific magnetic particles have a diffraction peak in the 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by X-ray diffraction.
[0037] However, in this specification, it is said that a material "has a crystalline structure" when it has a diffraction peak in the 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by X-ray diffraction method and the half-value width of this diffraction peak is 5° or less.
[0038] In the above X-ray diffraction pattern, the half-width of the diffraction peak appearing in the 2θ range of 42 to 48° is preferably 0.2 to 3°, more preferably 0.2 to 2°, and even more preferably 0.2 to 1°. The smaller the half-width of the diffraction peak, the denser the crystal structure is, and the more excellent the acid resistance of the magnetic particle-containing film that is formed.
[0039] The size of the crystal structure is, for example, 1 to 100 nm, and preferably 10 to 40 nm. Note that the "size of the nanocrystal structure" referred to here corresponds to the perfect circle equivalent diameter of the nanocrystal portion (the area observed two-dimensionally on the TEM image) confirmed when the specific magnetic particle is observed with a TEM.
[0040] In addition, in the specific magnetic particles, the portion other than the nanocrystalline structure may be amorphous. In other words, the specific magnetic particles may have a nanocrystalline structure in an amorphous particle. The crystallization rate of the specific magnetic particles is not particularly limited, but is preferably, for example, 30 to 100 volume %, and more preferably 50 to 100 volume %.
[0041] The average particle size of the specific magnetic particles is the volume-based median diameter (D50) and is 2 to 30 μm. Here, the volume-based median diameter (D50) of the specific magnetic particles refers to the diameter at which the total volume of the specific magnetic particles on the larger diameter side and the smaller diameter side is equal when the specific magnetic particles are divided into two parts with a threshold particle diameter at which the cumulative volume of all the specific magnetic particles is 50%. When the average particle size (D50) of the specific magnetic particles is 2 μm or more, the magnetic permeability of the magnetic particle-containing film formed is excellent, whereas when the average particle size (D50) of the specific magnetic particles is 30 μm or less, the sedimentation stability of the specific magnetic particles in the composition is excellent. The upper limit of the average particle size (D50) of the specific magnetic particles is preferably 28 μm or less, and more preferably 25 μm or less, in terms of superior effects of the present invention. The volume-based median diameter (D50) of the specific magnetic particles can be measured by a laser diffraction / scattering type particle size distribution measuring device. For example, a laser diffraction / scattering type particle size distribution measuring device LA-960 (model number) manufactured by Horiba, Ltd. can be used as the measuring device. However, the measuring device is not limited to this.
[0042] The aspect ratio of the specific magnetic particles is less than 8. When the aspect ratio of the specific magnetic particles is less than 8, the specific magnetic particles have excellent sedimentation stability in the composition, and the magnetic particle-containing film formed has excellent magnetic permeability. The aspect ratio of the specific magnetic particles is preferably less than 7, and more preferably 6 or less, in terms of the excellent sedimentation stability of the specific magnetic particles in the composition. The lower limit of the aspect ratio of the specific magnetic particles is not particularly limited, but it is preferably 1 or more. In this specification, the aspect ratio of a particle is calculated as follows: the particle for which the aspect ratio is to be calculated is observed under a transmission electron microscope (TEM), and 200 particles are randomly selected from the observation, and the longest width A of the particle is divided by the shortest width B (A / B) of each particle. The average of the 200 "A / B" values calculated is regarded as the aspect ratio of the particle.
[0043] The shape of the specific magnetic particles may be any of plate-like, elliptical, spherical, and amorphous, so long as the above-mentioned requirements regarding the average particle size and aspect ratio are satisfied.
[0044] The method for producing the specific magnetic particles is not particularly limited. One embodiment of the method for producing specific magnetic particles is a method of carrying out a heat treatment on Fe-group-containing amorphous particles that contain 70 to 90% by mass of Fe atoms, have an average particle size of 2 to 30 μm, and have an aspect ratio of less than 8. Specifically, the method involves first preparing Fe-group-containing amorphous particles of the above composition, and then heat treating the amorphous particles at a high temperature (for example, about 400 to 600° C.) to form a crystal structure within the amorphous particles. Another embodiment of the method for producing specific magnetic particles is a method in which Fe-group-containing amorphous particles containing 70 to 90% by mass of Fe atoms are heat-treated to form a crystal structure in the amorphous particles, and then the average particle size and aspect ratio are adjusted to a predetermined range by a predetermined dispersion treatment. The procedure for the heat treatment is as described above. As the specific magnetic particles, for example, commercially available products such as "KUAMET NC1" (manufactured by Epson Atmix Corporation) can also be used.
[0045] The specific magnetic particles may have a surface layer on their surfaces. By having the specific magnetic particles have a surface layer in this way, the specific magnetic particles can be endowed with a function according to the material of the surface layer. The surface layer may be an inorganic layer or an organic layer.
[0046] As the compound for forming the inorganic layer, metal oxides, metal nitrides, metal carbides, metal phosphate compounds, metal borate compounds, or silicate compounds (e.g., silicate esters such as tetraethyl orthosilicate, and silicates such as sodium silicate) are preferred, since they can form a surface layer excellent in at least one of insulation, gas barrier properties, and chemical stability. Specific examples of elements contained in these compounds include Fe, Al, Ca, Mn, Zn, Mg, V, Cr, Y, Ba, Sr, Ge, Zr, Ti, Si, and rare earth elements. Materials constituting the inorganic layer obtained using the compound for forming an inorganic layer include silicon oxide, germanium oxide, titanium oxide, aluminum oxide, zirconium oxide, and magnesium oxide, and the inorganic layer may be a layer containing two or more of these.
[0047] Examples of the organic layer-forming compound include acrylic monomers. Specific examples of the acrylic monomer include the compounds described in paragraphs 0022 to 0023 of JP2019-067960A. Examples of materials constituting the organic layer obtained by using the organic layer-forming compound include acrylic resins.
[0048] The thickness of the surface layer is not particularly limited, but is preferably from 3 to 1000 nm in order to better exhibit the function of the surface layer.
[0049] The content of the specific magnetic particles in the composition is preferably 70 to 90% by mass based on the total mass of the composition. In particular, the lower limit of the content of the specific magnetic particles is more preferably 75% by mass or more, in order to obtain a more excellent magnetic permeability of the magnetic particle-containing film formed. Also, the upper limit of the content of the specific magnetic particles is more preferably 85% by mass or less, in order to obtain a more excellent coating suitability of the composition. The content of the specific magnetic particles in the composition is preferably 70 to 90% by mass based on the total solid content of the composition. The specific magnetic particles may be used alone or in combination of two or more kinds.
[0050] [Rheology control agent] The composition includes a rheology control agent. The rheology control agent is a component that imparts thixotropic properties to the composition, ie, high viscosity when the shear stress (shear rate) is low and low viscosity when the shear stress (shear rate) is high. The content of the rheology control agent is preferably from 0.1 to 35 mass %, more preferably from 0.5 to 30 mass %, further preferably from 0.5 to 27 mass %, particularly preferably from 1 to 27 mass %, based on the total mass of the composition. The content of the rheology control agent is preferably from 0.1 to 35 mass%, more preferably from 0.5 to 30 mass%, further preferably from 0.5 to 27 mass%, particularly preferably from 1 to 27 mass%, based on the total solid content of the composition.
[0051] The rheology control agent may be an organic rheology control agent or an inorganic rheology control agent, with the organic rheology control agent being preferred.
[0052] <Organic rheology control agent> The content of the organic rheology control agent is preferably from 0.1 to 35 mass %, more preferably from 0.5 to 30 mass %, further preferably from 0.5 to 25 mass %, particularly preferably from 1 to 25 mass %, based on the total mass of the composition. The content of the organic rheology control agent is preferably from 0.1 to 35 mass %, more preferably from 0.5 to 30 mass %, further preferably from 0.5 to 25 mass %, particularly preferably from 1 to 25 mass %, based on the total solid content of the composition. The organic rheology control agents may be used alone or in combination of two or more kinds.
[0053] Examples of the organic rheology control agent include compounds having one or more (preferably two or more) adsorptive groups and further having a steric repulsive structural group. The adsorptive groups interact with the surface of the specific magnetic particles to cause the organic rheology control agent to be adsorbed onto the surface of the specific magnetic particles. Examples of the adsorptive group include an acid group, a basic group, and an amide group. Examples of the acid group include a carboxy group, a phosphate group, a sulfo group, a phenolic hydroxyl group, and an acid anhydride group thereof (such as an acid anhydride group of a carboxy group), and the carboxy group is preferred in terms of providing better effects of the present invention. Examples of basic groups include amino groups (groups in which one hydrogen atom has been removed from ammonia, primary amines, or secondary amines) and imino groups. Among these, the adsorptive group is preferably a carboxy group or an amide group, and more preferably a carboxy group. The steric repulsive structural group has a three-dimensionally bulky structure, and thus introduces steric hindrance to the specific magnetic particles to which the organic rheology control agent is adsorbed, thereby maintaining an appropriate space between the specific magnetic particles. As the steric repulsive structural group, for example, a chain group is preferable, a long-chain fatty acid group is more preferable, and a long-chain alkyl group is even more preferable. The organic rheology control agent also preferably has a hydrogen bonding unit. The hydrogen-bonding unit is a partial structure that functions to construct a hydrogen-bonding network between organic rheology control agents and between an organic rheology control agent and another component. The organic rheology control agent that contributes to the formation of the network may or may not be adsorbed to the surface of the specific magnetic particles. The hydrogen-bonding unit may be the same as or different from the above-mentioned adsorptive group. When the hydrogen-bonding unit is the same as the above-mentioned adsorptive group, a part of the adsorptive group binds to the surface of the specific magnetic particle, and another part functions as the hydrogen-bonding unit. The hydrogen-bonding unit is preferably a carboxy group or an amide group. The carboxy group as the hydrogen-bonding unit is preferred because it is easily incorporated in the curing reaction when producing a magnetic particle-containing film, and the amide group is preferred because the composition has better stability over time.
[0054] When the organic rheology control agent is a resin, the organic rheology control agent may have a repeating unit containing a graft chain described below, or may not substantially have such a repeating unit. When the organic rheology control agent is a resin and does not substantially have a repeating unit containing a graft chain described below, the content of the repeating unit containing a graft chain described below relative to the total mass of the organic rheology control agent is preferably less than 2% by mass, more preferably 1% by mass or less, and even more preferably less than 0.1% by mass. The lower limit is 0% by mass or more.
[0055] The organic rheology control agent is preferably one or more selected from the group consisting of polycarboxylic acids (compounds having two or more carboxy groups), polycarboxylic anhydrides (compounds having two or more acid anhydride groups consisting of carboxy groups), and amide waxes. These may be resins or materials other than resins. These may also correspond to an aggregation control agent and / or an aggregation dispersant, which will be described later.
[0056] Examples of organic rheology control agents include modified urea, urea modified polyamide, fatty acid amide, polyurethane, polyamide amide, polymeric urea derivatives, and salts thereof (such as carboxylates). The modified urea is a reaction product of an isocyanate monomer or its adduct with an organic amine. The modified urea is modified with polyoxyalkylene polyol (polyoxyethylene polyol, polyoxypropylene polyol, etc.) and / or alkyd chain, etc. The urea modified polyamide is, for example, a compound containing a urea bond and a compound having a medium polarity group or a low polarity group introduced at the end of the compound. Examples of the medium polarity group or low polarity group include polyoxyalkylene polyol (polyoxyethylene polyol, polyoxypropylene polyol, etc.) and an alkyd chain. The fatty acid amide is a compound having a long chain fatty acid group and an amide group in the molecule. These may be resins or non-resins. These may also correspond to an aggregation control agent and / or an aggregation dispersant, which will be described later.
[0057] The molecular weight of the organic rheology control agent (weight average molecular weight when the agent has a molecular weight distribution) is preferably in the range of 200 to 50,000. When the organic rheology control agent has an acid value, the acid value is preferably from 5 to 400 mgKOH / g. When the organic rheology control agent has an amine acid value, the amine value is preferably from 5 to 300 mgKOH / g.
[0058] (Aggregation control agent) Organic rheology control agents also include aggregation control agents, which may be resins or other substances. The aggregation control agent has the function of binding to relatively dense aggregates such as certain magnetic particles, and further dispersing other optional components (e.g., polymerizable compounds, etc.) in the composition to create bulky aggregates. When the composition contains an aggregation control agent, the specific magnetic particles in the composition are prevented from forming a hard cake, and bulkier aggregates are formed, which can improve redispersibility.
[0059] The aggregation control agent may, for example, be a cellulose derivative. Examples of the cellulose derivatives include carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl ethyl cellulose, and salts thereof.
[0060] When the composition contains an aggregation control agent, the content of the aggregation control agent is preferably 0.1 to 20 mass %, preferably 0.3 to 15 mass %, and more preferably 0.5 to 10 mass %, based on the total mass of the composition. The content of the aggregation control agent is preferably from 0.1 to 20 mass %, more preferably from 0.3 to 15 mass %, and further preferably from 0.5 to 10 mass %, based on the total solid content of the composition.
[0061] (Aggregation and dispersant) The organic rheology control agent also includes a flocculating dispersant. The flocculating dispersant may be a resin or may be something other than a resin. The flocculating dispersant has a function of adsorbing to the surface of the specific magnetic particles, separating the specific magnetic particles from each other, while maintaining the distance between the specific magnetic particles at a certain level or more through the interaction between the dispersants, thereby preventing the specific magnetic particles from directly flocculating with each other. As a result, the flocculation of the specific magnetic particles is suppressed, and even if an aggregate is formed, the aggregate has a relatively low density. Furthermore, other components (e.g., polymerizable compounds, etc.) optionally contained in the composition can be dispersed in the composition to form a bulky aggregate, which can improve redispersibility.
[0062] As the flocculating dispersant, an alkylol ammonium salt of a polybasic acid is preferred. The polybasic acid may have two or more acid groups, and examples thereof include acidic polymers containing repeating units having an acid group (e.g., polyacrylic acid, polymethacrylic acid, polyvinylsulfonic acid, polyphosphoric acid, etc.). Other examples of polybasic acids include polymers obtained by polymerizing unsaturated fatty acids such as crotonic acid. Alkylolammonium salts of polybasic acids can be obtained by reacting these polybasic acids with alkylolammonium. The salts obtained by such reactions usually contain the following partial structure: -C(=O)-N(-R 1 )(-R 2 -OH) Here, R 1 is an alkyl group, R 2 is an alkylene group. The alkylol ammonium salt of a polybasic acid is preferably a polymer containing a plurality of the above partial structures. When the alkylol ammonium salt of a polybasic acid is a polymer, the weight average molecular weight is preferably 1,000 to 100,000, more preferably 5,000 to 20,000. The polymer of the alkylol ammonium salt of a polybasic acid is bonded to the surface of the specific magnetic particles and is also hydrogen bonded to other flocculating dispersant molecules, so that the main chain structure of the polymer can penetrate between the specific magnetic particles and separate the specific magnetic particles from each other.
[0063] One of the preferred embodiments of the flocculating dispersant is amide wax, which is a dehydration condensation product of at least any acid selected from (a) saturated aliphatic monocarboxylic acids and hydroxyl group-containing aliphatic monocarboxylic acids, and (b) polybasic acids, and (c) at least any amine selected from diamines and tetraamines. The above (a) to (c) are preferably used in such a manner that the molar ratio of (a):(b):(c)=1-3:0-5:1-6.
[0064] The saturated aliphatic monocarboxylic acids preferably have a carbon number of 12 to 22. Specific examples include lauric acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, nonadecanoic acid, arachidic acid, and behenic acid. The hydroxyl group-containing aliphatic monocarboxylic acids preferably have a carbon number of 12 to 22. Specific examples include 12-hydroxystearic acid and dihydroxystearic acid. These saturated aliphatic monocarboxylic acids and hydroxyl group-containing aliphatic monocarboxylic acids may be used alone or in combination.
[0065] The polybasic acids are preferably dibasic or higher carboxylic acids having 2 to 12 carbon atoms, and more preferably dicarboxylic acids. Examples of such dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid, aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid, and alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and cyclohexylsuccinic acid. These polybasic acids may be used alone or in combination.
[0066] The diamines preferably have a carbon number of 2 to 14. Specific examples include ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, hexamethylenediamine, metaxylenediamine, tolylenediamine, paraxylenediamine, phenylenediamine, isophoronediamine, 1,10-decanediamine, 1,12-dodecanediamine, 4,4-diaminodicyclohexylmethane, and 4,4-diaminodiphenylmethane. The tetraamines preferably have a carbon number of 2 to 14. Specific examples include butane-1,1,4,4-tetraamine and pyrimidine-2,4,5,6-tetraamine. These diamines and tetraamines may be used alone or in combination.
[0067] The amount of diamines and tetraamines is adjusted according to the number of moles of saturated aliphatic monocarboxylic acid or hydroxyl group-containing aliphatic monocarboxylic acid and the number of moles of polybasic acids so that the total number of carboxyl groups and the total number of amino groups are equivalent. For example, when there are n moles (n=0-5) of aliphatic dicarboxylic acid, which is a polybasic acid, for 2 moles of aliphatic monocarboxylic acid, and the number of moles of diamines is (n+1), the acid and amine are equivalent.
[0068] The amide wax may be obtained as a mixture of a plurality of compounds having different molecular weights. The amide wax is preferably a compound represented by the following chemical formula (I). The amide wax may be a single compound or a mixture. AC-(BC) m -A···(I) In formula (I), A is a dehydroxylated residue of a saturated aliphatic monocarboxylic acid and / or a hydroxyl group-containing saturated aliphatic monocarboxylic acid, B is a dehydroxylated residue of a polybasic acid, C is a dehydrogenated residue of a diamine and / or a tetraamine, and m is 0≦m≦5.
[0069] One preferred embodiment of the aggregation dispersant is a compound represented by the following formula (II).
[0070] [ka]
[0071] In formula (II), R 1 represents a monovalent linear aliphatic hydrocarbon group having 10 to 25 carbon atoms, R 2 and R 3 each independently represents a divalent aliphatic hydrocarbon group having 2, 4, 6, or 8 carbon atoms, a divalent alicyclic hydrocarbon group having 6 carbon atoms, or a divalent aromatic hydrocarbon group; R 4 represents a divalent aliphatic hydrocarbon group having 1 to 8 carbon atoms, R 5 and R 6 each independently represents a monovalent aliphatic hydrocarbon group having 1 to 3 carbon atoms or a hydroxyalkyl ether group. In formula (II), L1 ~L 3 each independently represents an amide bond, L 1 and L 3 If -CONH-, then L 2 is -NHCO-, and L 1 and L 3 When is -NHCO-, L 2 is -CONH-.
[0072] R 1 is a monovalent linear aliphatic hydrocarbon group having 10 to 25 carbon atoms, and examples thereof include linear alkyl groups such as a decyl group, a lauryl group, a myristyl group, a pentadecyl group, a stearyl group, a palmityl group, a nonadecyl group, an eicosyl group, and a behenyl group; linear alkenyl groups such as a decenyl group, a pentadecenyl group, an oleyl group, and an eicosenyl group; and linear alkynyl groups such as a pentadecynyl group, an octadecynyl group, and a nonadecynyl group. Among them, R 1 is preferably a monovalent linear aliphatic hydrocarbon group having 14 to 25 carbon atoms, more preferably a monovalent linear aliphatic hydrocarbon group having 18 to 21 carbon atoms. The linear aliphatic hydrocarbon group is preferably an alkyl group.
[0073] R 2 and R 3 Examples of the divalent aliphatic hydrocarbon group having 2, 4, 6 or 8 carbon atoms include an ethylene group, an n-butylene group, an n-hexylene group, and an n-octylene group. R 2 and R 3 Examples of the divalent alicyclic hydrocarbon group having 6 carbon atoms include a 1,4-cyclohexylene group, a 1,3-cyclohexylene group, and a 1,2-cyclohexylene group. R 2 and R 3 Examples of the divalent aromatic hydrocarbon group in include arylene groups having 6 to 10 carbon atoms, such as a 1,4-phenylene group, a 1,3-phenylene group, and a 1,2-phenylene group.
[0074] Among them, R 2 and R3 is preferably a divalent aliphatic hydrocarbon group having 2, 4, 6 or 8 carbon atoms, more preferably a divalent aliphatic hydrocarbon group having 2, 4 or 6 carbon atoms, still more preferably a divalent aliphatic hydrocarbon group having 2 or 4 carbon atoms, and still more preferably a divalent aliphatic hydrocarbon group having 2 carbon atoms. The divalent aliphatic hydrocarbon group is preferably a linear alkylene group.
[0075] R 4 represents a divalent aliphatic hydrocarbon group having 1 to 8 carbon atoms, and among these, a linear or branched alkylene group is preferred, and a linear alkylene group is more preferred, in that they have an excellent thickening effect. Also, R 4 The divalent aliphatic hydrocarbon group in has 1 to 8 carbon atoms, and from the viewpoint of excellent thickening effect, it is preferably 1 to 7, more preferably 3 to 7, further preferably 3 to 6, and particularly preferably 3 to 5. Therefore, R 4 is preferably a linear or branched alkylene group having 1 to 8 carbon atoms, more preferably a linear alkylene group having 1 to 7 carbon atoms, still more preferably a linear alkylene group having 3 to 7 carbon atoms, particularly preferably a linear alkylene group having 3 to 6 carbon atoms, and most preferably a linear alkylene group having 3 to 5 carbon atoms.
[0076] R 5 and R 6 Examples of the monovalent aliphatic hydrocarbon group having 1 to 3 carbon atoms include linear or branched alkyl groups having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, a propyl group, and an isopropyl group; linear or branched alkenyl groups having 2 to 3 carbon atoms, such as a vinyl group, a 1-methylvinyl group, and a 2-propenyl group; and linear or branched alkynyl groups having 2 to 3 carbon atoms, such as an ethynyl group and a propynyl group.
[0077] R 5 and R 6 Examples of the hydroxyalkyl ether group in the formula (I) include mono- or di(hydroxy)C groups such as a 2-hydroxyethoxy group, a 2-hydroxypropoxy group, and a 2,3-dihydroxypropoxy group. 1-3Examples of such groups include alkyl ether groups.
[0078] Among them, R 5 and R 6 are each independently preferably a monovalent aliphatic hydrocarbon group having 1 to 3 carbon atoms, more preferably a linear or branched alkyl group having 1 to 3 carbon atoms, still more preferably a linear alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group.
[0079] As the compound represented by formula (II), the compounds represented by the following formulae (II-1) to (II-9) are preferred.
[0080] [ka]
[0081] Examples of the flocculating dispersant include ANTI-TERRA-203, 204, 206, and 250 (all trade names, manufactured by BYK); ANTI-TERRA-U (trade name, manufactured by BYK); DISPER BYK-102, 180, and 191 (all trade names, manufactured by BYK); BYK-P105 (trade name, manufactured by BYK); TEGO Disper 630 and 700 (all trade names, manufactured by Evonik Degussa Japan); TALENE VA-705B (trade name, manufactured by Kyoeisha Chemical Co., Ltd.); and FLOWNON RCM-300TL and RCM-230AF (trade names, manufactured by Kyoeisha Chemical Co., Ltd., Amide Wax).
[0082] When the composition contains an aggregating dispersant, the content of the aggregating dispersant is preferably from 0.1 to 35 mass %, more preferably from 0.3 to 30 mass %, and further preferably from 0.5 to 27 mass %, based on the total mass of the composition. The content of the aggregation dispersant is preferably from 0.1 to 35 mass %, more preferably from 0.3 to 30 mass %, and further preferably from 0.5 to 27 mass %, based on the total solid content of the composition.
[0083] <Inorganic rheology control agent> Inorganic rheology control agents include, for example, bentonite, silica, calcium carbonate, and smectite.
[0084] [Other resins] The composition also preferably contains other resins. The above-mentioned "other resins" refer to resins that do not fall under the category of rheology control agents which are resins. The other resins preferably have a weight average molecular weight of more than 2,000.
[0085] Other resins include (meth)acrylic resins, epoxy resins, enethiol resins, polycarbonate resins, polyether resins, polyarylate resins, polysulfone resins, polyethersulfone resins, polyphenylene resins, polyarylene ether phosphine oxide resins, polyimide resins, polyamideimide resins, polyolefin resins, cyclic olefin resins, polyester resins, styrene resins, and phenoxy resins. One of these resins may be used alone, or two or more may be mixed and used. As the cyclic olefin resin, norbornene resins are preferred from the viewpoint of improving heat resistance. Commercially available norbornene resins include, for example, the ARTON series (e.g., ARTON F4520) manufactured by JSR Corporation. Examples of epoxy resins include epoxy resins which are glycidyl ethers of phenolic compounds, epoxy resins which are glycidyl ethers of various novolac resins, alicyclic epoxy resins, aliphatic epoxy resins, heterocyclic epoxy resins, glycidyl ester epoxy resins, glycidylamine epoxy resins, epoxy resins obtained by glycidylating halogenated phenols, condensates of silicon compounds having epoxy groups and other silicon compounds, copolymers of polymerizable unsaturated compounds having epoxy groups and other polymerizable unsaturated compounds, etc. Also, examples of epoxy resins that can be used include Marproof G-0150M, G-0105SA, G-0130SP, G-0250SP, G-1005S, G-1005SA, G-1010S, G-2050M, G-01100, and G-01758 (manufactured by NOF Corp., epoxy group-containing polymers). In addition, the other resins may be those described in the examples of WO 2016 / 088645. In addition, when the other resins have an ethylenically unsaturated group, particularly a (meth)acryloyl group, in a side chain, it is also preferable that the main chain and the ethylenically unsaturated group are bonded via a divalent linking group having an alicyclic structure.
[0086] One of the preferred embodiments of the other resins is a resin having a polymerizable group such as an unsaturated double bond (e.g., an ethylenically unsaturated double bond), an epoxy group, or an oxetanyl group. When the polymerizable group reacts during the formation of the magnetic particle-containing film, a magnetic particle-containing film having excellent mechanical strength is obtained. Examples of such other resins include polymers having epoxy groups in their side chains, and polymerizable monomers or oligomers having two or more epoxy groups in their molecules. Specific examples of such resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, and aliphatic epoxy resins. These other resins may be commercially available products or may be obtained by introducing an epoxy group into the side chain of a polymer. For commercially available products, see, for example, paragraph 0191 of JP 2012-155288 A, the contents of which are incorporated herein by reference. Other examples include ADEKA RESIN EP-4000S, EP-4003S, EP-4010S, and EP-4011S (all manufactured by ADEKA Corporation), NC-2000, NC-3000, NC-7300, XD-1000, EPPN-501, and EPPN-502 (all manufactured by ADEKA Corporation), and JER1031S. Furthermore, commercially available products of phenol novolac type epoxy resins include JER-157S65, JER-152, JER-154, and JER-157S70 (all manufactured by Mitsubishi Chemical Corporation). Specific examples of polymers having oxetanyl groups in their side chains and polymerizable monomers or oligomers having two or more oxetanyl groups in the molecule include Aron Oxetane OXT-121, OXT-221, OX-SQ, and PNOX (all manufactured by Toagosei Co., Ltd.). When synthesizing other resins having epoxy groups by introducing epoxy groups into the polymer side chains, the introduction reaction can be carried out by reacting for a predetermined time at a reaction temperature of 50 to 150°C in an organic solvent using, for example, a tertiary amine such as triethylamine or benzylmethylamine, a quaternary ammonium salt such as dodecyltrimethylammonium chloride, tetramethylammonium chloride or tetraethylammonium chloride, pyridine, triphenylphosphine, or the like as a catalyst. The amount of the alicyclic epoxy unsaturated compound introduced can be controlled so that the acid value of the resulting polymer is in the range of 5 to 200 KOH mg / g. The weight average molecular weight can be in the range of 500 to 5,000,000, preferably 1,000 to 500,000. Instead of the alicyclic epoxy unsaturated compound, compounds having a glycidyl group as an epoxy group such as glycidyl (meth)acrylate and allyl glycidyl ether can also be used. For such compounds, see, for example, paragraph 0045 of JP-A-2009-265518, the contents of which are incorporated herein by reference.
[0087] One of the preferred embodiments of the other resin is a resin having an acid group, a basic group, or an amide group. The other resin having an acid group, a basic group, or an amide group is preferred because it easily functions as a dispersant for dispersing magnetic particles and provides a superior effect of the present invention. Examples of the acid group include a carboxy group, a phosphate group, a sulfo group, and a phenolic hydroxyl group. The carboxy group is preferred in terms of obtaining superior effects of the present invention. Examples of the basic group include an amino group (a group in which one hydrogen atom has been removed from ammonia, a primary amine, or a secondary amine) and an imino group. In particular, in terms of obtaining superior effects of the present invention, it is preferable that the other resin has a carboxy group or an amide group.
[0088] When the other resin has an acid group, the acid value of the other resin is preferably from 10 to 500 mgKOH / g, particularly preferably from 30 to 400 mgKOH / g, in terms of better effects of the present invention.
[0089] As the other resin, it is preferable to use another resin having a solubility in the solvent of 10 g / L or more, and it is more preferable to use another resin having a solubility in the solvent of 20 g / L or more, since this improves the dispersibility of the other resin in the composition and makes the effects of the present invention more excellent. The upper limit of the solubility of the other resin in the solvent is preferably 2000 g / L or less, particularly preferably 1000 g / L or less. The solubility of a resin in a solvent means the amount (g) of the resin that can be dissolved in 1 L of the solvent at 25°C.
[0090] The content of the other resins is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, even more preferably 2 to 15 mass%, and particularly preferably 2.5 to 10 mass%, relative to the total mass of the composition, in terms of better effects of the present invention. The content of the other resins is preferably from 0.1 to 30 mass %, more preferably from 1 to 20 mass %, further preferably from 2 to 15 mass %, particularly preferably from 2.5 to 10 mass %, based on the total solid content of the composition.
[0091] <Resin having a repeating unit containing a graft chain (Resin A)> Examples of other resins include a resin having a repeating unit containing a graft chain (hereinafter, also referred to as "resin A"). Resin A can enhance the effect of improving the stability over time of the composition by supporting the effect of the rheology control agent.
[0092] When the composition contains resin A, the content of resin A is preferably 0.1 to 30 mass%, more preferably 0.5 to 20 mass%, and even more preferably 1 to 10 mass%, relative to the total mass of the composition, in terms of better effects of the present invention. The content of the resin A is preferably from 0.1 to 30 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %, based on the total solid content of the composition. When resin A is used, the mass ratio of the content of the rheology control agent to the content of resin A (rheology control agent / resin A) is preferably 10 / 90 to 90 / 10, more preferably 30 / 70 to 80 / 20, and even more preferably 50 / 50 to 70 / 30.
[0093] (Repeating unit including graft chain) In the repeating unit containing the graft chain, the longer the graft chain, the higher the steric repulsion effect and the better the dispersibility of the specific magnetic particles. On the other hand, if the graft chain is too long, the adsorptive force to the specific magnetic particles decreases, and the dispersibility of the specific magnetic particles tends to decrease. For this reason, the graft chain preferably has an atomic number excluding hydrogen atoms of 40 to 10,000, more preferably an atomic number excluding hydrogen atoms of 50 to 2,000, and even more preferably an atomic number excluding hydrogen atoms of 60 to 500. Here, the graft chain refers to a chain extending from the root of the main chain (an atom attached to the main chain in a group branching from the main chain) to the end of the group branching from the main chain.
[0094] In addition, the graft chain preferably contains a polymer structure. Examples of such polymer structures include a poly(meth)acrylate structure (e.g., a poly(meth)acrylic structure), a polyester structure, a polyurethane structure, a polyurea structure, a polyamide structure, and a polyether structure. In order to improve the interaction between the graft chain and the solvent and thereby enhance the dispersibility of the specific magnetic particles, the graft chain is preferably a graft chain containing at least one structure selected from the group consisting of a polyester structure, a polyether structure, and a poly(meth)acrylate structure, and more preferably a graft chain containing at least one of a polyester structure and a polyether structure.
[0095] Resin A may be a resin obtained by using a macromonomer containing a graft chain (a monomer having a polymer structure and bonding to a main chain to form a graft chain). The macromonomer containing a graft chain (a monomer having a polymer structure and bonding to a main chain to form a graft chain) is not particularly limited, but a macromonomer containing a reactive double bond group can be preferably used.
[0096] Commercially available macromonomers corresponding to the repeating units containing the graft chain and suitable for use in the synthesis of resin A include AA-6, AA-10, AB-6, AS-6, AN-6, AW-6, AA-714, AY-707, AY-714, AK-5, AK-30, and AK-32 (all trade names, manufactured by Toagosei Co., Ltd.), as well as Blenmer PP-100, Blenmer PP-500, Blenmer PP-800, Blenmer PP-1000, Blenmer 55-PET-800, Blenmer PME-4000, Blenmer PSE-400, Blenmer PSE-1300, and Blenmer 43PAPE-600B (all trade names, manufactured by NOF Corp.). Among these, AA-6, AA-10, AB-6, AS-6, AN-6, or Blenmer PME-4000 are preferred.
[0097] Resin A preferably contains at least one structure selected from the group consisting of polymethyl acrylate, polymethyl methacrylate, and cyclic or linear polyester, more preferably contains at least one structure selected from the group consisting of polymethyl acrylate, polymethyl methacrylate, and linear polyester, and further preferably contains at least one structure selected from the group consisting of polymethyl acrylate structure, polymethyl methacrylate structure, polycaprolactone structure, and polyvalerolactone structure. Resin A may contain one of the above structures alone, or may contain a plurality of these structures. Here, the polycaprolactone structure refers to a structure containing a ring-opened ε-caprolactone structure as a repeating unit, and the polyvalerolactone structure refers to a structure containing a ring-opened δ-valerolactone structure as a repeating unit.
[0098] When resin A contains repeating units in which j and k are 5 in formula (1) described below and formula (2) described below, the above-mentioned polycaprolactone structure can be introduced into resin A. Furthermore, when resin A contains repeating units in which j and k are 4 in formula (1) described below and formula (2) described below, the above-mentioned polyvalerolactone structure can be introduced into the resin. In addition, the resin A is X in the formula (4) described below. 5 is a hydrogen atom, and R 4 When the resin A contains a repeating unit in which is a methyl group, the above-mentioned polymethyl acrylate structure can be introduced into the resin A. In addition, the resin A is X in the formula (4) described below. 5 is a methyl group, and R 4 When the resin A contains a repeating unit in which is a methyl group, the above-mentioned polymethyl methacrylate structure can be introduced into the resin A.
[0099] Resin A preferably contains, as a repeating unit including a graft chain, a repeating unit represented by any one of the following formulae (1) to (4), and more preferably contains a repeating unit represented by any one of the following formulae (1A), (2A), (3A), (3B), and (4).
[0100] [ka]
[0101] In formulas (1) to (4), W 1 , W 2 , W 3 , and W 4 Each independently represents an oxygen atom or NH. 1 , W 2 , W 3 , and W 4 is preferably an oxygen atom. In formulas (1) to (4), X 1 , X 2 , X 3 , X 4 , and X 5Each of X independently represents a hydrogen atom or a monovalent organic group. 1 , X 2 , X 3 , X 4 , and X 5 From the viewpoint of synthesis constraints, each of the is preferably a hydrogen atom or an alkyl group having 1 to 12 carbon atoms (number of carbon atoms), more preferably a hydrogen atom or a methyl group, and further preferably a methyl group.
[0102] In formulas (1) to (4), Y 1 , Y 2 , Y 3 , and Y 4 Each of Y independently represents a divalent linking group, and the linking group is not particularly limited in structure. 1 , Y 2 , Y 3 , and Y 4 Specific examples of the divalent linking group represented by the formula include the following linking groups (Y-1) to (Y-21). In the structures shown below, A and B respectively represent the bonding sites with the left and right terminal groups in formulas (1) to (4). Among the structures shown below, (Y-2) or (Y-13) is more preferred from the viewpoint of ease of synthesis.
[0103] [ka]
[0104] In formulas (1) to (4), Z 1 , Z 2 , Z 3 , and Z 4 Each of Z independently represents a hydrogen atom or a monovalent substituent. The structure of the above-mentioned substituent is not particularly limited, but specific examples thereof include an alkyl group, a hydroxyl group, an alkoxy group, an aryloxy group, a heteroaryloxy group, an alkylthioether group, an arylthioether group, a heteroarylthioether group, and an amino group. Among these, Z 1 , Z 2 , Z 3 , and Z 4As the group represented by the formula (I), a group having a steric repulsion effect is preferable, particularly from the viewpoint of improving dispersibility, and each independently an alkyl group or alkoxy group having 5 to 24 carbon atoms is more preferable, and among these, each independently a branched alkyl group having 5 to 24 carbon atoms, a cyclic alkyl group having 5 to 24 carbon atoms, or an alkoxy group having 5 to 24 carbon atoms is even more preferable. The alkyl group contained in the alkoxy group may be linear, branched, or cyclic. Also, Z 1 , Z 2 , Z 3 , and Z 4 The substituent represented by the formula (I) is preferably a group containing a curable group such as a (meth)acryloyl group, an epoxy group, and / or an oxetanyl group. Examples of the group containing a curable group include "-O-alkylene group-(-O-alkylene group-) AL -(meth)acryloyloxy group". AL represents an integer of 0 to 5, preferably 1. The above alkylene groups each independently preferably have 1 to 10 carbon atoms. When the above alkylene group has a substituent, the substituent is preferably a hydroxyl group. The above-mentioned substituent may be a group containing an onium structure. The onium structure-containing group is a group having an anion moiety and a cation moiety. The anion moiety is, for example, an oxygen anion (-O - ) containing partial structures. Among them, oxygen anions (-O - ) is preferably directly bonded to the end of the repeating structure to which n, m, p, or q is added in the repeating units represented by formula (1) to (4), and is preferably bonded to the end of the repeating structure to which n is added in the repeating unit represented by formula (1) (i.e., -(-OC j H 2j -CO-) n It is more preferable that the aryl group is directly bonded to the aryl group (the right end in -). The cation of the cationic moiety of the group containing an onium structure can be, for example, an ammonium cation. When the cationic moiety is an ammonium cation, the cationic moiety is a cationic nitrogen atom (>N + It is a partial structure containing a cationic nitrogen atom (>N+ <) is preferably bonded to four substituents (preferably organic groups), of which 1 to 4 are preferably alkyl groups having 1 to 15 carbon atoms. It is also preferable that one or more (preferably one) of the four substituents is a group containing a curable group such as a (meth)acryloyl group, an epoxy group, and / or an oxetanyl group. Examples of the group containing a curable group that the substituent may be include the above-mentioned "-O-alkylene group-(-O-alkylene group-)" as mentioned above. AL -(meth)acryloyloxy group.
[0105] In the formulas (1) to (4), n, m, p, and q each independently represent an integer of 1 to 500. In the formulae (1) and (2), j and k each independently represent an integer of 2 to 8. In the formulae (1) and (2), j and k each preferably represent an integer of 4 to 6, and more preferably 5. In addition, in formulas (1) and (2), n and m are, for example, integers of 2 or more, preferably integers of 6 or more, more preferably integers of 10 or more, and further preferably integers of 20 or more. In addition, when resin A contains a polycaprolactone structure and a polyvalerolactone structure, the sum of the repeat number of the polycaprolactone structure and the repeat number of the polyvalerolactone structure is preferably an integer of 10 or more, and more preferably an integer of 20 or more.
[0106] In formula (3), R 3 represents a branched or linear alkylene group, preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 2 or 3 carbon atoms. 3 may be the same or different from each other. In formula (4), R 4 R represents a hydrogen atom or a monovalent organic group, and the structure of this monovalent substituent is not particularly limited. 4 R is preferably a hydrogen atom, an alkyl group, an aryl group, or a heteroaryl group, and more preferably a hydrogen atom or an alkyl group. 4When is an alkyl group, the alkyl group is preferably a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, or a cyclic alkyl group having 5 to 20 carbon atoms, more preferably a linear alkyl group having 1 to 20 carbon atoms, and further preferably a linear alkyl group having 1 to 6 carbon atoms. In formula (4), when q is 2 to 500, a plurality of X present in the graft chain 5 and R 4 may be the same or different from each other.
[0107] Resin A may contain repeating units having two or more different structures, including a graft chain. That is, the molecule of resin A may contain repeating units represented by formulas (1) to (4) having structures different from one another, and when n, m, p, and q in formulas (1) to (4) each represent an integer of 2 or more, in formulas (1) and (2), j and k may have structures different from one another in the side chain, and in formulas (3) and (4), R present in a plurality of units in the molecule may be present. 3 , R 4 , and X 5 may be the same or different from each other.
[0108] The repeating unit represented by formula (1) is more preferably a repeating unit represented by the following formula (1A). The repeating unit represented by formula (2) is more preferably a repeating unit represented by the following formula (2A).
[0109] [ka]
[0110] In formula (1A), X 1 , Y 1 , Z 1 , and n is X in formula (1). 1 , Y 1 , Z 1 In formula (2A), X has the same meaning as n, and the preferred range is also the same. 2 , Y 2 , Z 2, and m is X in formula (2). 2 , Y 2 , Z 2 , and m have the same meaning and preferred range.
[0111] The repeating unit represented by formula (3) is more preferably a repeating unit represented by the following formula (3A) or (3B).
[0112] [ka]
[0113] In formula (3A) or (3B), X 3 , Y 3 , Z 3 , and p is X in formula (3). 3 , Y 3 , Z 3 , and p have the same meanings and preferred ranges.
[0114] Resin A more preferably contains a repeating unit represented by formula (1A) as a repeating unit including a graft chain.
[0115] Resin A also preferably contains a repeating unit containing a polyalkyleneimine structure and a polyester structure. The repeating unit containing a polyalkyleneimine structure and a polyester structure preferably contains a polyalkyleneimine structure in the main chain and a polyester structure as a graft chain.
[0116] The polyalkyleneimine structure is a polymerized structure containing two or more identical or different alkyleneimine chains. Specific examples of the alkyleneimine chain include those represented by the following formula (4A) and formula (4B).
[0117] [ka]
[0118] In formula (4A), R X1 and R X2 each independently represents a hydrogen atom or an alkyl group. 1 represents an integer greater than or equal to 2. 1 represents a bonding position to a polyester chain, an adjacent alkyleneimine chain, or a hydrogen atom or a substituent.
[0119] [ka]
[0120] In formula (4B), R X3 and R X4 each independently represents a hydrogen atom or an alkyl group. 2 represents an integer of 2 or more. The alkyleneimine chain represented by formula (4B) is a polyester chain having an anionic group and a N + The anionic groups contained in the polyester chain form salt bridges, resulting in bonding.
[0121] * in formula (4A) and formula (4B), and * in formula (4B) 2 each independently represents a position at which the group is bonded to an adjacent alkyleneimine chain, or a hydrogen atom or a substituent. In the formula (4A) and the formula (4B), it is particularly preferable that the * represents the position at which the alkyleneimine chain is bonded to the adjacent alkyleneimine chain.
[0122] R in formula (4A) X1 and R X2 and R in formula (4B) X3 and R X4 each independently represents a hydrogen atom or an alkyl group. The alkyl group preferably has 1 to 6 carbon atoms, and more preferably has 1 to 3 carbon atoms. In formula (4A), R X1 and R X2 are preferably all hydrogen atoms. In formula (4B), R X3 and R X4are preferably all hydrogen atoms.
[0123] a in formula (4A) 1 and a in formula (4B) 2 is not particularly limited as long as it is an integer of 2 or more. The upper limit is preferably 10 or less, more preferably 6 or less, even more preferably 4 or less, still more preferably 2 or 3, and particularly preferably 2.
[0124] In formula (4A) and formula (4B), * represents the bonding position to the adjacent alkyleneimine chain, or to a hydrogen atom or a substituent. Examples of the substituent include an alkyl group (for example, an alkyl group having 1 to 6 carbon atoms), etc. Furthermore, a polyester chain may be bonded as the substituent.
[0125] The alkyleneimine chain represented by formula (4A) is the same as that described above. 1 Specifically, it is preferable that the carbonyl carbon in the polyester chain is linked to the polyester chain at the position of 1 It is preferred that the bond is at the position The polyester chain may be represented by the following formula (5A).
[0126] [ka]
[0127] When the alkyleneimine chain is an alkyleneimine chain represented by formula (4B), the polyester chain is anionic (preferably an oxygen anion O - ), and the anionic group and the N in formula (4B) + It is preferred that these form a salt bridge. An example of such a polyester chain is a polyester chain represented by the following formula (5B).
[0128] [ka]
[0129] L in formula (5A) X1 and L in formula (5B) X2 each independently represents a divalent linking group. The divalent linking group is preferably an alkylene group having 3 to 30 carbon atoms.
[0130] b in formula (5A) 11 and b in formula (5B) 21 each independently represents an integer of 2 or more, preferably an integer of 6 or more, and the upper limit thereof is, for example, 200 or less.
[0131] b in formula (5A) 12 and b in formula (5B) 22 each independently represents 0 or 1.
[0132] X in formula (5A) A and X in formula (5B) B each independently represents a hydrogen atom or a substituent. Examples of the substituent include an alkyl group, an alkoxy group, a polyalkyleneoxyalkyl group, and an aryl group.
[0133] The number of carbon atoms in the alkyl group (which may be linear, branched, or cyclic) and the alkyl group contained in the alkoxy group (which may be linear, branched, or cyclic) can be 1 to 30, and preferably 1 to 10. The alkyl group may further have a substituent, and examples of the substituent include a hydroxyl group and a halogen atom (examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom).
[0134] Polyalkyleneoxyalkyl groups are R X6 (OR X7 ) p (O) q R is a substituent represented by the formula: X6 represents an alkyl group, R X7 represents an alkylene group, p represents an integer of 2 or more, and q represents 0 or 1. RX6 The alkyl group represented by X A In addition, R X7 The alkylene group represented by the formula X A Examples of the alkyl group include those obtained by removing one hydrogen atom from the alkyl group represented by the following formula: p is an integer of 2 or more, and its upper limit is, for example, 10 or less, and preferably 5 or less.
[0135] The aryl group may be, for example, an aryl group having 6 to 24 carbon atoms (which may be either monocyclic or polycyclic). The aryl group may further have a substituent, and examples of the substituent include an alkyl group, a halogen atom, and a cyano group.
[0136] The polyester chain is preferably a structure obtained by ring-opening a lactone such as ε-caprolactone, δ-caprolactone, β-propiolactone, γ-butyrolactone, δ-valerolactone, γ-valerolactone, enantholactone, β-butyrolactone, γ-hexanolactone, γ-octanolactone, δ-hexalanolactone, δ-octanolactone, δ-dodecanolactone, α-methyl-γ-butyrolactone, or lactide (which may be either L- or D-form), and more preferably a structure obtained by ring-opening ε-caprolactone or δ-valerolactone.
[0137] The repeating unit containing the polyalkyleneimine structure and the polyester structure can be synthesized according to the synthesis method described in Japanese Patent No. 5,923,557.
[0138] In the resin A, the content of the repeating unit containing a graft chain is, in mass terms, for example, 2 to 100 mass%, preferably 2 to 95 mass%, more preferably 2 to 90 mass%, and still more preferably 5 to 30 mass%, relative to the total mass of the resin A. When the repeating unit containing a graft chain is contained within this range, the effects of the present invention are more excellent.
[0139] (hydrophobic repeating unit) Resin A may also contain a hydrophobic repeating unit different from the repeating unit containing a graft chain (i.e., not corresponding to the repeating unit containing a graft chain). However, in this specification, a hydrophobic repeating unit is a repeating unit that does not have an acid group (e.g., a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, a phenolic hydroxyl group, etc.).
[0140] The hydrophobic repeating unit is preferably a repeating unit derived from (corresponding to) a compound (monomer) having a ClogP value of 1.2 or more, and more preferably a repeating unit derived from a compound having a ClogP value of 1.2 to 8. This makes it possible to more reliably exhibit the effects of the present invention.
[0141] The ClogP value is a value calculated by the program "CLOGP" available from Daylight Chemical Information System, Inc. This program provides a "calculated logP" value calculated by the fragment approach of Hansch and Leo (see the literature below). The fragment approach is based on the chemical structure of a compound, and divides the chemical structure into partial structures (fragments), and estimates the logP value of the compound by summing up the logP contributions assigned to the fragments. Details are described in the literature below. In this specification, the ClogP value calculated by the program CLOGP v4.82 is used. AJ Leo, Comprehensive Medicinal Chemistry, Vol.4, C. Hansch, PG Sammnens, JB Taylor and CA Ramsden, Eds., p.295, Pergamon Press, 1990 C. Hansch & AJ Leo. SUbstituent Constants For Correlation Analysis in Chemistry and Biology. John Wiley & Sons. AJ Leo. Calculating logPoct from structure. Chem. Rev., 93, 1281-1306, 1993.
[0142] logP stands for the common logarithm of the partition coefficient P, and is a physical property that quantitatively represents how an organic compound is distributed in equilibrium in a two-phase system of oil (generally 1-octanol) and water, and is expressed by the following formula. logP = log(Coil / Cwater) In the formula, Coil represents the molar concentration of the compound in the oil phase, and Cwater represents the molar concentration of the compound in the water phase. As the logP value increases toward the positive side, around 0, the oil solubility increases, and as the absolute value increases toward the negative side, the water solubility increases. It has a negative correlation with the water solubility of organic compounds, and is widely used as a parameter to estimate the hydrophilicity or hydrophobicity of organic compounds.
[0143] Resin A preferably contains, as a hydrophobic repeating unit, one or more repeating units selected from repeating units derived from monomers represented by the following formulas (i) to (iii).
[0144] [ka]
[0145] In the above formulas (i) to (iii), R 1 , R 2 , and R3 each independently represents a hydrogen atom, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, etc.), or an alkyl group having 1 to 6 carbon atoms (for example, a methyl group, an ethyl group, a propyl group, etc.). R 1 , R 2 , and R 3 R is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom or a methyl group. 2 and R 3 is more preferably a hydrogen atom. X represents an oxygen atom (-O-) or an imino group (-NH-), and is preferably an oxygen atom.
[0146] L is a single bond or a divalent linking group. Examples of the divalent linking group include a divalent aliphatic group (e.g., an alkylene group, a substituted alkylene group, an alkenylene group, a substituted alkenylene group, an alkynylene group, and a substituted alkynylene group), a divalent aromatic group (e.g., an arylene group, and a substituted arylene group), a divalent heterocyclic group, an oxygen atom (-O-), a sulfur atom (-S-), an imino group (-NH-), and a substituted imino group (-NR 31 -, where R 31 is an aliphatic group, an aromatic group, or a heterocyclic group), a carbonyl group (-CO-), and combinations thereof.
[0147] The divalent aliphatic group may have a cyclic structure or a branched structure. The number of carbon atoms in the aliphatic group is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10. The aliphatic group may be an unsaturated aliphatic group or a saturated aliphatic group, but a saturated aliphatic group is preferred. The aliphatic group may have a substituent. Examples of the substituent include a halogen atom, an aromatic group, and a heterocyclic group.
[0148] The number of carbon atoms in the divalent aromatic group is preferably 6 to 20, more preferably 6 to 15, and further preferably 6 to 10. The aromatic group may have a substituent. Examples of the substituent include a halogen atom, an aliphatic group, an aromatic group, and a heterocyclic group.
[0149] The divalent heterocyclic group preferably contains a 5-membered or 6-membered ring as a heterocycle. The heterocycle may be condensed with another heterocycle, an aliphatic ring, or an aromatic ring. The heterocyclic group may have a substituent. Examples of the substituent include a halogen atom, a hydroxyl group, an oxo group (=O), a thioxo group (=S), an imino group (=NH), a substituted imino group (=NR 32 , where R 32 is an aliphatic group, an aromatic group, or a heterocyclic group), an aliphatic group, an aromatic group, and a heterocyclic group.
[0150] L is preferably a single bond, an alkylene group, or a divalent linking group containing an oxyalkylene structure. The oxyalkylene structure is more preferably an oxyethylene structure or an oxypropylene structure. L may also contain a polyoxyalkylene structure containing two or more repeated oxyalkylene structures. The polyoxyalkylene structure is preferably a polyoxyethylene structure or a polyoxypropylene structure. The polyoxyethylene structure is represented by -(OCH2CH2)n-, where n is preferably an integer of 2 or more, more preferably an integer of 2 to 10.
[0151] Z includes an aliphatic group (e.g., an alkyl group, a substituted alkyl group, an unsaturated alkyl group, a substituted unsaturated alkyl group), an aromatic group (e.g., an aryl group, a substituted aryl group, an arylene group, a substituted arylene group), a heterocyclic group, and combinations thereof. These groups include an oxygen atom (-O-), a sulfur atom (-S-), an imino group (-NH-), a substituted imino group (-NR 31 -, where R 31 may contain an aliphatic group, an aromatic group, or a heterocyclic group), or a carbonyl group (-CO-).
[0152] The aliphatic group may have a cyclic structure or a branched structure. The number of carbon atoms in the aliphatic group is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10. The aliphatic group further includes a ring assembly hydrocarbon group and a bridged cyclic hydrocarbon group. Examples of the ring assembly hydrocarbon group include a bicyclohexyl group, a perhydronaphthalenyl group, a biphenyl group, and a 4-cyclohexylphenyl group. Examples of the bridged cyclic hydrocarbon ring include bicyclic hydrocarbon rings such as pinane, bornane, norpinane, norbornane, and bicyclooctane rings (such as bicyclo[2.2.2]octane ring and bicyclo[3.2.1]octane ring), homobredane, adamantane, and tricyclo[5.2.1.0]octane ring. 2,6 ]decane and tricyclo[4.3.1.1 2,5 ]undecane ring and other tricyclic hydrocarbon rings, as well as tetracyclo[4.4.0.1 2,5 .1 7,10 ]dodecane, and tetracyclic hydrocarbon rings such as perhydro-1,4-methano-5,8-methanonaphthalene ring. The bridged cyclic hydrocarbon ring also includes condensed rings in which multiple 5- to 8-membered cycloalkane rings are condensed, such as perhydronaphthalene (decalin), perhydroanthracene, perhydrophenanthrene, perhydroacenaphthene, perhydrofluorene, perhydroindene, and perhydrophenalene rings. The aliphatic group is preferably a saturated aliphatic group rather than an unsaturated aliphatic group. The aliphatic group may have a substituent. Examples of the substituent include a halogen atom, an aromatic group, and a heterocyclic group. However, the aliphatic group does not have an acid group as a substituent.
[0153] The number of carbon atoms in the aromatic group is preferably 6 to 20, more preferably 6 to 15, and further preferably 6 to 10. The aromatic group may have a substituent. Examples of the substituent include a halogen atom, an aliphatic group, an aromatic group, and a heterocyclic group. However, the aromatic group does not have an acid group as a substituent.
[0154] The heterocyclic group preferably contains a 5- or 6-membered ring as a heterocycle. The heterocycle may be condensed with another heterocycle, an aliphatic ring, or an aromatic ring. The heterocyclic group may have a substituent. Examples of the substituent include a halogen atom, a hydroxyl group, an oxo group (=O), a thioxo group (=S), an imino group (=NH), a substituted imino group (=NR 32 , where R 32 is an aliphatic group, an aromatic group, or a heterocyclic group), an aliphatic group, an aromatic group, and a heterocyclic group, provided that the heterocyclic group does not have an acid group as a substituent.
[0155] In the above formula (iii), R 4 , R 5 , and R 6 R each independently represents a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, etc.), an alkyl group having 1 to 6 carbon atoms (e.g., a methyl group, an ethyl group, a propyl group, etc.), Z, or LZ, where L and Z are the same as the groups defined above. 4 , R 5 , and R 6 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom.
[0156] As the monomer represented by the above formula (i), R 1 , R 2 , and R 3 is a hydrogen atom or a methyl group, L is a single bond or a divalent linking group containing an alkylene group or an oxyalkylene structure, X is an oxygen atom or an imino group, and Z is an aliphatic group, a heterocyclic group, or an aromatic group. In addition, as the monomer represented by the above formula (ii), R 1 is a hydrogen atom or a methyl group, L is an alkylene group, and Z is an aliphatic group, a heterocyclic group, or an aromatic group. 4 , R 5 , and R 6 is a hydrogen atom or a methyl group, and Z is an aliphatic group, a heterocyclic group, or an aromatic group.
[0157] Representative examples of the compounds represented by formulas (i) to (iii) include radically polymerizable compounds selected from acrylic acid esters, methacrylic acid esters, styrenes, and the like. Representative examples of the compounds represented by formulas (i) to (iii) can be found in the compounds described in paragraphs 0089 to 0093 of JP-A No. 2013-249417, the contents of which are incorporated herein by reference.
[0158] In the resin A, the content of the hydrophobic repeating unit is preferably from 10 to 90 mass %, and more preferably from 20 to 80 mass %, based on the total mass of the resin A, in terms of mass.
[0159] (Functional group capable of forming an interaction with specific magnetic particles) Resin A may have a functional group capable of forming an interaction with the specific magnetic particles. It is preferable that resin A further contains a repeating unit containing a functional group capable of forming an interaction with the specific magnetic particles. Examples of functional groups capable of forming interactions with specific magnetic particles include acid groups, basic groups, coordinating groups, and reactive functional groups. When resin A contains an acid group, a basic group, a coordinating group, or a reactive functional group, it preferably contains a repeating unit containing an acid group, a repeating unit containing a basic group, a repeating unit containing a coordinating group, or a repeating unit having a reactive functional group, respectively.
[0160] The repeating unit containing an acid group may be the same as or different from the repeating unit containing the graft chain described above, but the repeating unit containing an acid group is a repeating unit different from the hydrophobic repeating unit described above (i.e., it does not correspond to the hydrophobic repeating unit described above).
[0161] Examples of the acid group, which is a functional group capable of forming an interaction with the specific magnetic particles, include a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, and a phenolic hydroxyl group, and at least one of the carboxylic acid group, the sulfonic acid group, and the phosphoric acid group is preferred, and the carboxylic acid group is more preferred. The carboxylic acid group has a good adsorption force to the specific magnetic particles and is highly dispersible. That is, it is preferable that resin A further contains a repeating unit containing at least one of a carboxylic acid group, a sulfonic acid group, and a phosphoric acid group.
[0162] Resin A may have one or more types of repeating units containing an acid group. When the resin A contains a repeating unit containing an acid group, the content thereof is preferably from 5 to 80 mass %, and more preferably from 10 to 60 mass %, based on the total mass of the resin A, in mass terms.
[0163] Examples of basic groups that are functional groups capable of forming an interaction with specific magnetic particles include primary amino groups, secondary amino groups, tertiary amino groups, heterocycles containing N atoms, and amide groups, and a preferred basic group is a tertiary amino group because of its good adsorption to specific magnetic particles and high dispersibility. Resin A may contain one or more of these basic groups. When the resin A contains a repeating unit containing a basic group, the content thereof is preferably from 0.01 to 50 mass %, and more preferably from 0.01 to 30 mass %, based on the total mass of the resin A, in mass conversion.
[0164] Examples of the coordinating group, which is a functional group capable of forming an interaction with the specific magnetic particles, and the reactive functional group include an acetylacetoxy group, a trialkoxysilyl group, an isocyanate group, an acid anhydride, and an acid chloride. A preferred functional group is an acetylacetoxy group, which has a good adsorption force to the specific magnetic particles and a high dispersibility of the specific magnetic particles. Resin A may have one or more of these groups. When resin A contains a repeating unit containing a coordinating group or a repeating unit containing a reactive functional group, the content of these units, calculated on a mass basis, is preferably 10 to 80 mass % and more preferably 20 to 60 mass % based on the total mass of resin A.
[0165] When the resin A contains functional groups capable of forming interactions with specific magnetic particles other than the graft chains, it is sufficient that the resin A contains functional groups capable of forming interactions with the above-mentioned various specific magnetic particles, and there is no particular restriction on how these functional groups are introduced. For example, it is preferable that the resin contained in the composition contains one or more repeating units selected from repeating units derived from monomers represented by the following formulas (iv) to (vi).
[0166] [ka]
[0167] In formulas (iv) to (vi), R 11 , R 12 , and R 13 each independently represents a hydrogen atom, a halogen atom (for example, a fluorine atom, a chlorine atom, a bromine atom, etc.), or an alkyl group having 1 to 6 carbon atoms (for example, a methyl group, an ethyl group, a propyl group, etc.). In formulas (iv) to (vi), R 11 , R 12 , and R 13 In general formula (iv), R is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom or a methyl group. 12 and R 13 is more preferably a hydrogen atom.
[0168] X1 in formula (iv) represents an oxygen atom (-O-) or an imino group (-NH-), and is preferably an oxygen atom. In addition, Y in the formula (v) represents a methine group or a nitrogen atom.
[0169] Furthermore, L1 in formulae (iv) and (v) represents a single bond or a divalent linking group. The definition of the divalent linking group is the same as the definition of the divalent linking group represented by L in formula (i) above.
[0170] L1 is preferably a single bond, an alkylene group, or a divalent linking group containing an oxyalkylene structure. The oxyalkylene structure is more preferably an oxyethylene structure or an oxypropylene structure. L1 may also contain a polyoxyalkylene structure containing two or more repeated oxyalkylene structures. The polyoxyalkylene structure is preferably a polyoxyethylene structure or a polyoxypropylene structure. The polyoxyethylene structure is represented by -(OCH2CH2)n-, where n is preferably an integer of 2 or more, more preferably an integer of 2 to 10.
[0171] In the formulae (iv) to (vi), Z1 represents a functional group capable of forming an interaction with the specific magnetic particle other than the graft chain, and is preferably a carboxylic acid group or a tertiary amino group, more preferably a carboxylic acid group.
[0172] In formula (vi), R 14 , R 15 , and R 16 R each independently represents a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, etc.), an alkyl group having 1 to 6 carbon atoms (e.g., a methyl group, an ethyl group, a propyl group, etc.), -Z1, or L1-Z1. Here, L1 and Z1 have the same meanings as L1 and Z1 above, and preferred examples are also the same. R 14 , R 15 , and R 16 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom.
[0173] As the monomer represented by formula (iv), R 11 , R 12 , and R 13are each independently a hydrogen atom or a methyl group, L1 is an alkylene group or a divalent linking group containing an oxyalkylene structure, X1 is an oxygen atom or an imino group, and Z1 is a carboxylic acid group. In addition, as the monomer represented by formula (v), R 11 is a hydrogen atom or a methyl group, L1 is an alkylene group, Z1 is a carboxylic acid group, and Y is a methine group. Further, as the monomer represented by formula (vi), R 14 , R 15 , and R 16 are each independently a hydrogen atom or a methyl group, and Z1 is a carboxylic acid group.
[0174] Representative examples of the monomers (compounds) represented by formulas (iv) to (vi) are shown below. Examples of the monomer include methacrylic acid, crotonic acid, isocrotonic acid, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule (e.g., 2-hydroxyethyl methacrylate) with succinic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with phthalic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with tetrahydroxyphthalic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with trimellitic anhydride, a reaction product of a compound containing an addition polymerizable double bond and a hydroxyl group in the molecule with pyromellitic anhydride, acrylic acid, acrylic acid dimer, acrylic acid oligomer, maleic acid, itaconic acid, fumaric acid, 4-vinylbenzoic acid, vinylphenol, and 4-hydroxyphenylmethacrylamide.
[0175] The content of the repeating unit containing a functional group capable of forming an interaction with the specific magnetic particles is, in terms of the interaction with the specific magnetic particles, stability over time, and permeability into the developer, preferably 0.05 to 90 mass %, more preferably 1.0 to 80 mass %, and even more preferably 10 to 70 mass %, relative to the total mass of resin A.
[0176] (ethylenically unsaturated group) Resin A may contain an ethylenically unsaturated group. The ethylenically unsaturated group is not particularly limited, but examples thereof include a (meth)acryloyl group, a vinyl group, and a styryl group, with a (meth)acryloyl group being preferred. Resin A preferably contains a repeating unit containing an ethylenically unsaturated group in the side chain, and more preferably contains a repeating unit containing an ethylenically unsaturated group in the side chain and derived from a (meth)acrylate (hereinafter also referred to as a "(meth)acrylic repeating unit containing an ethylenically unsaturated group in the side chain"). The (meth)acrylic repeating unit containing an ethylenically unsaturated group in the side chain can be obtained, for example, by subjecting an ethylenically unsaturated compound containing a glycidyl group or an alicyclic epoxy group to an addition reaction of the carboxylic acid group in the resin A containing a (meth)acrylic repeating unit containing a carboxylic acid group. In this way, a (meth)acrylic repeating unit containing an ethylenically unsaturated group in the side chain can be formed.
[0177] When the resin A contains a repeating unit containing an ethylenically unsaturated group, the content thereof is preferably from 30 to 70 mass %, and more preferably from 40 to 60 mass %, based on the total mass of the resin A, in mass terms.
[0178] (Other curing groups) Resin A may contain other curable groups in addition to the ethylenically unsaturated group. Other curable groups include, for example, epoxy groups and oxetanyl groups. Resin A preferably contains a repeating unit containing another curable group in the side chain, and more preferably contains a repeating unit containing another curable group in the side chain and derived from a (meth)acrylate (hereinafter also referred to as a "(meth)acrylic repeating unit containing another curable group in the side chain"). An example of a (meth)acrylic repeating unit containing another curable group in the side chain is glycidyl (meth)acrylate.
[0179] When the resin A contains a repeating unit containing another curable group, the content thereof is preferably from 5 to 50 mass %, and more preferably from 10 to 30 mass %, based on the total mass of the resin A, in mass conversion.
[0180] (Other repeating units) Furthermore, for the purpose of improving various properties such as film-forming ability, resin A may further contain other repeating units having various functions different from the repeating units described above, as long as the effects of the present invention are not impaired. Examples of such other repeating units include repeating units derived from radically polymerizable compounds selected from acrylonitriles and methacrylonitriles. Resin A may use one or more of these other repeating units, and the content thereof, calculated on a mass basis, is preferably from 0 to 80 mass %, more preferably from 10 to 60 mass %, based on the total mass of resin A.
[0181] (Physical properties of resin A) The acid value of resin A is not particularly limited, but is, for example, preferably 0 to 400 mgKOH / g, more preferably 10 to 350 mgKOH / g, further preferably 30 to 300 mgKOH / g, and particularly preferably in the range of 50 to 200 mgKOH / g. If the acid value of resin A is 50 mgKOH / g or more, the sedimentation stability of the specific magnetic particles can be further improved.
[0182] In this specification, the acid value can be calculated, for example, from the average content of acid groups in a compound. Also, a resin having a desired acid value can be obtained by changing the content of repeating units containing an acid group in the resin.
[0183] The weight average molecular weight of the resin A is not particularly limited, but is preferably, for example, 3,000 or more, more preferably 4,000 or more, even more preferably 5,000 or more, and particularly preferably 6,000 or more. The upper limit is, for example, preferably 300,000 or less, more preferably 200,000 or less, even more preferably 100,000 or less, and particularly preferably 50,000 or less. Resin A can be synthesized based on a known method.
[0184] As specific examples of Resin A, reference can be made to the polymer compounds described in paragraphs 0127 to 0129 of JP-A No. 2013-249417, the contents of which are incorporated herein by reference.
[0185] Furthermore, as the resin A, the graft copolymers described in paragraphs 0037 to 0115 of JP 2010-106268 A (corresponding paragraphs 0075 to 0133 of US 2011 / 0124824) can also be used, the contents of which are incorporated herein by reference.
[0186] <Alkali-soluble resin> The other resin may include an alkali-soluble resin. In this specification, the alkali-soluble resin refers to a resin that contains a group that promotes alkali solubility (alkali-soluble group, for example an acid group such as a carboxylic acid group), and refers to a resin different from the resin A described above.
[0187] Examples of the alkali-soluble resin include resins containing at least one alkali-soluble group in the molecule, such as polyhydroxystyrene resins, polysiloxane resins, (meth)acrylic resins, (meth)acrylamide resins, (meth)acrylic / (meth)acrylamide copolymers, epoxy resins, and polyimide resins.
[0188] Specific examples of alkali-soluble resins include copolymers of unsaturated carboxylic acids and ethylenically unsaturated compounds. The unsaturated carboxylic acid is not particularly limited, but examples thereof include monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and vinylacetic acid; dicarboxylic acids such as itaconic acid, maleic acid, and fumaric acid, or acid anhydrides thereof; and polycarboxylic acid monoesters such as mono(2-(meth)acryloyloxyethyl)phthalate.
[0189] Examples of the copolymerizable ethylenically unsaturated compound include methyl (meth)acrylate, etc. Compounds described in paragraph 0027 of JP 2010-097210 A and paragraphs 0036-0037 of JP 2015-068893 A can also be used, and the contents of the above are incorporated herein by reference.
[0190] In addition, a copolymerizable ethylenically unsaturated compound having an ethylenically unsaturated group in a side chain may be used in combination. In other words, the alkali-soluble resin may contain a repeating unit having an ethylenically unsaturated group in a side chain. The ethylenically unsaturated group contained in the side chain is preferably a (meth)acrylic acid group. A repeating unit containing an ethylenically unsaturated group in a side chain can be obtained, for example, by subjecting a carboxylic acid group of a (meth)acrylic repeating unit containing a carboxylic acid group to an addition reaction with an ethylenically unsaturated compound containing a glycidyl group or an alicyclic epoxy group.
[0191] The alkali-soluble resin is also preferably an alkali-soluble resin containing a curable group. Examples of the curable group include, but are not limited to, ethylenically unsaturated groups (e.g., (meth)acryloyl groups, vinyl groups, styryl groups, etc.) and cyclic ether groups (e.g., epoxy groups, oxetanyl groups, etc.). Among these, the curable group is preferably an ethylenically unsaturated group, and more preferably a (meth)acryloyl group, in terms of the ability to control polymerization by radical reaction. The alkali-soluble resin containing a curable group is preferably an alkali-soluble resin having a curable group in a side chain, etc. Examples of the alkali-soluble resin containing a curable group include Dianaru NR series (manufactured by Mitsubishi Rayon Co., Ltd.), Photomer 6173 (COOH-containing polyurethane acrylic oligomer, manufactured by Diamond Shamrock Co., Ltd.), Viscoat R-264, KS Resist 106 (all manufactured by Osaka Organic Chemical Industry Co., Ltd.), Cyclomer P series (e.g., ACA230AA), Plaxel CF200 series (all manufactured by Daicel Corporation), Ebecryl 3800 (manufactured by Daicel-Allnex Corporation), and Acricur RD-F8 (manufactured by Nippon Shokubai Co., Ltd.).
[0192] Examples of the alkali-soluble resin include radical polymers containing carboxylic acid groups in the side chains described in JP-A-59-044615, JP-B-54-034327, JP-B-58-12577, JP-B-54-25957, JP-A-54-92723, JP-A-59-053836, and JP-A-59-071048; Examples of binder resins that can be used include acetal-modified polyvinyl alcohol-based binder resins containing an alkali-soluble group as described in WO 001-318463; polyvinylpyrrolidone; polyethylene oxide; alcohol-soluble nylon, and polyethers which are reaction products of 2,2-bis-(4-hydroxyphenyl)-propane and epichlorohydrin; and polyimide resins as described in WO 2008 / 123097.
[0193] As the alkali-soluble resin, for example, the compounds described in paragraphs 0225 to 0245 of JP-A-2016-075845 can also be used, the contents of which are incorporated herein by reference.
[0194] As the alkali-soluble resin, a polyimide precursor can also be used. The polyimide precursor refers to a resin obtained by subjecting a compound containing an acid anhydride group and a diamine compound to an addition polymerization reaction at 40 to 100°C. Specific examples of the polyimide precursor include compounds described in paragraphs 0011 to 0031 of JP 2008-106250 A, compounds described in paragraphs 0022 to 0039 of JP 2016-122101 A, compounds described in paragraphs 0061 to 0092 of JP 2016-068401 A, resins described in paragraph 0050 of JP 2014-137523 A, resins described in paragraph 0058 of JP 2015-187676 A, and resins described in paragraphs 0012 to 0013 of JP 2014-106326 A, the contents of which are incorporated herein by reference.
[0195] As the alkali-soluble resin, a copolymer of benzyl (meth)acrylate / (meth)acrylic acid / if necessary, other addition-polymerizable vinyl monomers and a copolymer of allyl (meth)acrylate / (meth)acrylic acid / if necessary, other addition-polymerizable vinyl monomers are preferred, as they have an excellent balance of film strength, sensitivity, and developability. The other addition-polymerizable vinyl monomers may be used alone or in combination of two or more kinds. The copolymer preferably contains a curable group, and more preferably contains an ethylenically unsaturated group such as a (meth)acryloyl group, in order to provide a cured film with better moisture resistance. For example, a curable group may be introduced into the copolymer by using a monomer having a curable group as the other addition polymerizable vinyl monomer. Also, a curable group (preferably an ethylenically unsaturated group such as a (meth)acryloyl group) may be introduced into a part or all of one or more of the units derived from (meth)acrylic acid and / or the other addition polymerizable vinyl monomer in the copolymer. Examples of the other addition-polymerizable vinyl monomers include methyl (meth)acrylate, styrene-based monomers (such as hydroxystyrene), and ether dimers. Examples of the ether dimer include a compound represented by the following general formula (ED1) and a compound represented by the following general formula (ED2).
[0196] [ka]
[0197] In general formula (ED1), R 1 and R 2 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 25 carbon atoms.
[0198] [ka]
[0199] In the general formula (ED2), R represents a hydrogen atom or an organic group having a carbon number of 1 to 30. Specific examples of the general formula (ED2) can be found in JP-A-2010-168539.
[0200] For specific examples of the ether dimer, see, for example, paragraph 0317 of JP 2013-029760 A, the contents of which are incorporated herein by reference. The ether dimer may be of only one type, or of two or more types.
[0201] The acid value of the alkali-soluble resin is not particularly limited, but in general, it is preferably from 30 to 500 mgKOH / g, and more preferably from 50 to 200 mgKOH / g or more.
[0202] When the composition contains an alkali-soluble resin, the content of the alkali-soluble resin is preferably from 0.1 to 40 mass %, more preferably from 0.5 to 30 mass %, and even more preferably from 1 to 20 mass %, based on the total mass of the composition. When the composition contains an alkali-soluble resin, the content of the alkali-soluble resin is preferably from 0.1 to 40 mass %, more preferably from 0.5 to 30 mass %, and even more preferably from 1 to 20 mass %, based on the total solid content of the composition.
[0203] [Polymerizable compound] The composition of the present invention may contain a polymerizable compound as a component different from the above-mentioned components.
[0204] The content of the polymerizable compound is preferably from 1 to 35 mass %, more preferably from 1 to 30 mass %, and further preferably from 3 to 27 mass %, based on the total mass of the composition. The content of the polymerizable compound is preferably from 1 to 35 mass %, more preferably from 1 to 30 mass %, and further preferably from 3 to 27 mass %, based on the total solid content of the composition. The molecular weight (or weight average molecular weight) of the polymerizable compound is not particularly limited, but is preferably 2000 or less.
[0205] <Compound containing a group containing an ethylenically unsaturated bond> One embodiment of the polymerizable compound is a compound that includes a group containing an ethylenically unsaturated bond (hereinafter, also simply referred to as an "ethylenically unsaturated group"). That is, in one embodiment of the composition of the present invention, it is preferable that the composition contains, as a polymerizable compound, a low molecular weight compound containing an ethylenically unsaturated group. The polymerizable compound is preferably a compound containing one or more ethylenically unsaturated bonds, more preferably a compound containing two or more, even more preferably a compound containing three or more, and particularly preferably a compound containing five or more. The upper limit is, for example, 15 or less. Examples of the ethylenically unsaturated group include a vinyl group, a (meth)allyl group, and a (meth)acryloyl group.
[0206] As the polymerizable compound, for example, the compounds described in paragraph 0050 of JP-A-2008-260927 and paragraph 0040 of JP-A-2015-068893 can be used, the contents of which are incorporated herein by reference.
[0207] The polymerizable compound may be in any chemical form, such as a monomer, a prepolymer, an oligomer, a mixture thereof, or a polymer thereof. The polymerizable compound is preferably a 3- to 15-functional (meth)acrylate compound, and more preferably a 3- to 6-functional (meth)acrylate compound.
[0208] The polymerizable compound is also preferably a compound containing one or more ethylenically unsaturated groups and having a boiling point of 100° C. or higher under normal pressure. For example, the compounds described in paragraphs
[0227] of JP-A-2013-029760 and paragraphs
[0254] to
[0257] of JP-A-2008-292970 can be referred to, the contents of which are incorporated herein by reference.
[0209] The polymerizable compound is preferably dipentaerythritol triacrylate (commercially available product is KAYARAD D-330; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol tetraacrylate (commercially available product is KAYARAD D-320; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol penta(meth)acrylate (commercially available product is KAYARAD D-310; manufactured by Nippon Kayaku Co., Ltd.), dipentaerythritol hexa(meth)acrylate (commercially available products are KAYARAD DPHA; manufactured by Nippon Kayaku Co., Ltd., A-DPH-12E; manufactured by Shin-Nakamura Chemical Co., Ltd.), and a structure in which the (meth)acryloyl group of these is mediated by an ethylene glycol residue or a propylene glycol residue (for example, SR454, SR499, commercially available from Sartomer Co., Ltd.). Oligomer types of these can also be used. In addition, NK Ester A-TMMT (pentaerythritol tetraacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.), A-TMMT (polyfunctional acrylate, manufactured by Toa Gosei Co., Ltd.), KAYARAD RP-1040, KAYARAD DPEA-12LT, KAYARAD DPHA LT, KAYARAD RP-3060, and KAYARAD DPEA-12 (all trade names, manufactured by Nippon Kayaku Co., Ltd.), etc. may also be used.
[0210] The polymerizable compound may have an acid group such as a carboxylic acid group, a sulfonic acid group, and a phosphoric acid group. The polymerizable compound containing an acid group is preferably an ester of an aliphatic polyhydroxy compound and an unsaturated carboxylic acid, more preferably the polymerizable compound in which an acid group is provided by reacting an unreacted hydroxyl group of an aliphatic polyhydroxy compound with a non-aromatic carboxylic anhydride, and more preferably the compound in which the aliphatic polyhydroxy compound is pentaerythritol and / or dipentaerythritol in the ester. Examples of commercially available products include Aronix TO-2349, M-305, M-510, and M-520 manufactured by Toagosei Co., Ltd.
[0211] The acid value of the polymerizable compound containing an acid group is preferably 0.1 to 40 mgKOH / g, more preferably 5 to 30 mgKOH / g. If the acid value of the polymerizable compound is 0.1 mgKOH / g or more, the development dissolution property is good, and if it is 40 mgKOH / g or less, it is advantageous in terms of production and / or handling. Furthermore, the photopolymerization performance is good and the curing property is excellent.
[0212] In a preferred embodiment, the polymerizable compound is a compound containing a caprolactone structure. The compound containing a caprolactone structure is not particularly limited as long as it contains a caprolactone structure in the molecule, and examples thereof include ε-caprolactone-modified polyfunctional (meth)acrylates obtained by esterifying a polyhydric alcohol such as trimethylolethane, ditrimethylolethane, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, diglycerol, or trimethylolmelamine with (meth)acrylic acid and ε-caprolactone. Among these, a compound containing a caprolactone structure represented by the following formula (Z-1) is preferred.
[0213] [ka]
[0214] In formula (Z-1), all of the six R's are groups represented by the following formula (Z-2), or 1 to 5 of the six R's are groups represented by the following formula (Z-2), and the remainder are groups represented by the following formula (Z-3).
[0215] [ka]
[0216] In formula (Z-2), R 1 represents a hydrogen atom or a methyl group, m represents the number 1 or 2, and "*" represents a bond.
[0217] [ka]
[0218] In formula (Z-3), R 1 represents a hydrogen atom or a methyl group, and "*" represents a bond.
[0219] The above polymerizable compound containing a caprolactone structure is commercially available, for example, from Nippon Kayaku as the KAYARAD DPCA series, and is DPCA-20 (in the above formulas (Z-1) to (Z-3), m=1, the number of groups represented by formula (Z-2)=2, R 1 are all hydrogen atoms), DPCA-30 (same formula, m=1, the number of groups represented by formula (Z-2)=3, R 1 are all hydrogen atoms), DPCA-60 (same formula, m=1, the number of groups represented by formula (Z-2)=6, R 1 are all hydrogen atoms), and DPCA-120 (wherein m=2, the number of groups represented by formula (Z-2)=6, R 1 are all hydrogen atoms). In addition, a commercially available product of the polymerizable compound containing a caprolactone structure is M-350 (trade name) (trimethylolpropane triacrylate) manufactured by Toagosei Co., Ltd.
[0220] As the polymerizable compound, a compound represented by the following formula (Z-4) or (Z-5) can also be used.
[0221] [ka]
[0222] In formulas (Z-4) and (Z-5), E is -((CH2) y CH2O)- or ((CH2) y CH(CH3)O)-, y represents an integer of 0 to 10, and X represents a (meth)acryloyl group, a hydrogen atom, or a carboxylic acid group. In formula (Z-4), the total number of (meth)acryloyl groups is 3 or 4; m represents an integer of 0 to 10; the sum of the m's is an integer of 0 to 40. In formula (Z-5), the total number of (meth)acryloyl groups is 5 or 6; n represents an integer of 0 to 10; and the sum of the n's is an integer of 0 to 60.
[0223] In formula (Z-4), m is preferably an integer of 0 to 6, and more preferably an integer of 0 to 4. The sum of the m's is preferably an integer of 2 to 40, more preferably an integer of 2 to 16, and further preferably an integer of 4 to 8. In the formula (Z-5), n is preferably an integer of 0 to 6, and more preferably an integer of 0 to 4. The sum of each n is preferably an integer of 3 to 60, more preferably an integer of 3 to 24, and further preferably an integer of 6 to 12. In addition, -((CH2) y CH2O)- or ((CH2) y In the case of CH(CH3)O)-, the terminal on the oxygen atom side is preferably bonded to X.
[0224] The compound represented by formula (Z-4) or formula (Z-5) may be used alone or in combination of two or more. In particular, in formula (Z-5), the form in which all six Xs are acryloyl groups, and in formula (Z-5), the mixture of the compound in which all six Xs are acryloyl groups and the compound in which at least one of the six Xs is a hydrogen atom are preferred. With this configuration, the developability can be further improved.
[0225] The total content of the compound represented by formula (Z-4) or formula (Z-5) in the polymerizable compound is preferably 20% by mass or more, and more preferably 50% by mass or more. Among the compounds represented by formula (Z-4) or formula (Z-5), pentaerythritol derivatives and / or dipentaerythritol derivatives are more preferred.
[0226] The polymerizable compound may contain a cardo skeleton. As the above-mentioned polymerizable compound containing a cardo skeleton, the above-mentioned polymerizable compound containing a 9,9-bisarylfluorene skeleton is preferable. The above-mentioned polymerizable compound containing a cardo skeleton is not limited, but examples thereof include Oncoat EX series (manufactured by Nagase & Co., Ltd.) and OGSOL (manufactured by Osaka Gas Chemicals Co., Ltd.). The polymerizable compound is also preferably a compound containing an isocyanuric acid skeleton as a central core. An example of such a polymerizable compound is NK Ester A-9300 (manufactured by Shin-Nakamura Chemical Co., Ltd.). The content of the ethylenically unsaturated group in the polymerizable compound (meaning the value obtained by dividing the number of ethylenically unsaturated groups in the polymerizable compound by the molecular weight (g / mol) of the polymerizable compound) is preferably 5.0 mmol / g or more. The upper limit is not particularly limited, but is generally 20.0 mmol / g or less.
[0227] <Compound containing at least one of an epoxy group and an oxetanyl group> One embodiment of the polymerizable compound includes a compound containing at least one of an epoxy group and an oxetanyl group. That is, in one embodiment, the composition of the present invention preferably contains a compound containing at least one of an epoxy group and an oxetanyl group as a polymerizable compound. The polymerizable compound is preferably a compound containing one or more epoxy groups and / or oxetanyl groups, more preferably a compound containing two or more epoxy groups and / or oxetanyl groups. The upper limit is, for example, 10 or less. Among them, the polymerizable compound is more preferably an epoxy-curable compound having an epoxy group (epoxy compound). In the above polymerizable compound, the epoxy group and / or oxetanyl group (preferably the epoxy group) may be condensed with a cyclic group (such as an alicyclic group). The cyclic group condensed with the epoxy group and / or oxetanyl group preferably has 5 to 15 carbon atoms. In the above cyclic group, the portion other than the condensed epoxy group and / or oxetanyl group may be a monocyclic or polycyclic ring. Only one epoxy group or oxetanyl group may be condensed with one cyclic group, or two or more epoxy groups and / or oxetanyl groups may be condensed with one cyclic group.
[0228] The polymerizable compound may, for example, be a monofunctional or polyfunctional glycidyl ether compound. The polymerizable compound may be, for example, a (poly)alkylene glycol diglycidyl ether.
[0229] The polymerizable compound may be a compound containing a caprolactone structure represented by the above formula (Z-1), in which the group represented by formula (Z-2) is changed to the following formula (Z-2E) and the group represented by formula (Z-3) is changed to the group represented by formula (Z-3E).
[0230] [ka]
[0231] In formula (Z-2E), m represents the number 1 or 2, X and Y each independently represent a hydrogen atom or a substituent (preferably an alkyl group, preferably having 1 to 3 carbon atoms), and "*" represents a bond. In formula (Z-3E), X and Y each independently represent a hydrogen atom or a substituent (preferably an alkyl group, preferably having 1 to 3 carbon atoms), and "*" represents a bond.
[0232] The polymerizable compound may be a compound represented by the above formula (Z-4) modified so that X represents a group represented by formula (Z-3E) or a hydrogen atom. In the formula (Z-4) modified in this way, the total number of groups represented by formula (Z-3E) is 2 to 4.
[0233] The polymerizable compound may be a compound represented by the above formula (Z-5) modified so that X represents a group represented by formula (Z-3E) or a hydrogen atom. In the formula (Z-5) modified in this way, the total number of groups represented by formula (Z-3E) is 2 to 6 (preferably 5 or 6).
[0234] The polymerizable compound may be a compound having a structure in which N (number of) cyclic groups condensed with an epoxy group and / or an oxetanyl group are bonded via a linking group. N is an integer of 2 or more, preferably an integer of 2 to 6, and more preferably 2. The total number of atoms other than hydrogen atoms in the linking group is preferably 1 to 20, and more preferably 2 to 6. When N is 2, examples of the linking group include an alkyleneoxycarbonyl group.
[0235] Commercially available polymerizable compounds include polyfunctional aliphatic glycidyl ether compounds such as Denacol EX-212L, EX-214L, EX-216L, EX-321L, and EX-850L (all manufactured by Nagase ChemteX Corp.). These are low-chlorine products, but not low-chlorine products such as EX-212, EX-214, EX-216, EX-321, EX-614, and EX-850 can also be used. In addition, a commercially available product such as Celloxide 2021P (manufactured by Daicel Corporation, a multifunctional epoxy monomer) can also be used.
[0236] The composition may contain, as the polymerizable compound, both a compound containing a group containing an ethylenically unsaturated bond and a compound containing one or more of an epoxy group and an oxetanyl group. In this case, the mass ratio of their contents (the content of "compound containing a group containing an ethylenically unsaturated bond" / the content of "compound containing one or more of an epoxy group and an oxetanyl group") is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 80 / 20, and even more preferably 30 / 70 to 70 / 30.
[0237] [Curing Accelerator] The composition may also include a cure accelerator. In particular, when the composition contains a compound having an epoxy group and / or an oxetanyl group as the polymerizable compound, it is preferable to contain a curing accelerator. Examples of the curing accelerator include triphenylphosphine, methyltributylphosphonium dimethylphosphate, tris-orthotolylphosphine, and boron trifluoride amine complex. Other examples include 2-methylimidazole (trade name: 2MZ), 2-undecylimidazole (trade name: C11-Z), 2-heptadecylimidazole (trade name: C17Z), 1,2-dimethylimidazole (trade name: 1.2DMZ), 2-ethyl-4-methylimidazole (trade name: 2E4MZ), 2-phenylimidazole (trade name: 2PZ), 2-phenyl-4-methylimidazole (trade name: 2P4MZ), 1-benzyl-2-methylimidazole (trade name: 1B2 ... 1-cyanoethyl-2-phenylimidazole (trade name; 1B2PZ), 1-cyanoethyl-2-methylimidazole (trade name; 2MZ-CN), 1-cyanoethyl-2-undecylimidazole (trade name; C11Z-CN), 1-cyanoethyl-2-phenylimidazolium trimellitate (trade name; 2PZCNS-PW), 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine (trade name; 2MZ-A), 2,4-diamino-6-[2'-undecylimidazolyl -(1')]-ethyl-s-triazine (trade name; C11Z-A), 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine (trade name; 2E4MZ-A), 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct (trade name; 2MA-OK), 2-phenyl-4,5-dihydroxymethylimidazole (trade name; 2PHZ-PW), 2-phenyl-4-methyl-5- ... Examples of imidazole-based curing accelerators include phenylimidazole (trade name: 2P4MHZ-PW), 1-cyanoethyl-2-phenylimidazole (trade name: 2PZ-CN), 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine (trade name: 2MZA-PW), and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct (trade name: 2MAOK-PW) (all manufactured by Shikoku Chemical Industry Co., Ltd.).Further, examples of triarylphosphine-based curing accelerators include the compounds described in JP-A-2004-043405, paragraph 0052. Examples of phosphorus-based curing accelerators in which triphenylborane is added to triarylphosphine include the compounds described in JP-A-2014-005382, paragraph 0024. The content of the curing accelerator is preferably from 0.0002 to 3 mass %, more preferably from 0.002 to 2 mass %, and even more preferably from 0.02 to 1 mass %, based on the total mass of the composition. The content of the curing accelerator is preferably from 0.0002 to 3 mass %, more preferably from 0.002 to 2 mass %, and even more preferably from 0.02 to 1 mass %, based on the total solid content of the composition.
[0238] [Polymerization initiator] The composition may include a polymerization initiator. The polymerization initiator is not particularly limited, and a known polymerization initiator can be used. Examples of the polymerization initiator include a photopolymerization initiator and a thermal polymerization initiator, and a photopolymerization initiator is preferable. In addition, the polymerization initiator is preferably a so-called radical polymerization initiator. When the composition contains a polymerization initiator, the content thereof is preferably from 0.3 to 15 mass %, more preferably from 0.3 to 10 mass %, and further preferably from 0.3 to 8.0 mass %, based on the total mass of the composition. When the composition contains a polymerization initiator, the content thereof is preferably from 0.3 to 15 mass %, more preferably from 0.3 to 10 mass %, and further preferably from 0.3 to 8.0 mass %, based on the total solid content of the composition.
[0239] <Thermal polymerization initiator> Examples of the thermal polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile (AIBN), 3-carboxypropionitrile, azobismalenonitrile, and dimethyl-(2,2')-azobis(2-methylpropionate) [V-601], and organic peroxides such as benzoyl peroxide, lauroyl peroxide, and potassium persulfate. Specific examples of the polymerization initiator include those described on pages 65 to 148 of "Ultraviolet Curing System" by Kiyomi Kato (published by Sogo Gijutsu Center Co., Ltd. in 1989).
[0240] <Photopolymerization initiator> The photopolymerization initiator is not particularly limited as long as it can initiate polymerization of the polymerizable compound, and a known photopolymerization initiator can be used. For example, the photopolymerization initiator is preferably a photopolymerization initiator having photosensitivity to the ultraviolet region to the visible light region. In addition, it may be an activator that generates an active radical by reacting with a photoexcited sensitizer, or an initiator that initiates cationic polymerization according to the type of polymerizable compound. The photopolymerization initiator preferably contains at least one compound having a molar absorption coefficient of at least 50 within a range of 300 to 800 nm (more preferably 330 to 500 nm).
[0241] Examples of the photopolymerization initiator include halogenated hydrocarbon derivatives (e.g., compounds containing a triazine skeleton, compounds containing an oxadiazole skeleton, etc.), acylphosphine compounds such as acylphosphine oxides, hexaarylbiimidazoles, oxime compounds such as oxime derivatives, organic peroxides, thio compounds, ketone compounds, aromatic onium salts, aminoacetophenone compounds, and hydroxyacetophenones. Specific examples of photopolymerization initiators can be found in, for example, paragraphs 0265 to 0268 of JP2013-029760A, the contents of which are incorporated herein by reference.
[0242] More specifically, for example, the aminoacetophenone-based initiators described in JP-A-10-291969 and the acylphosphine-based initiators described in Japanese Patent No. 4225898 can also be used as the photopolymerization initiator. As the hydroxyacetophenone compound, for example, Omnirad-184, Omnirad-1173, Omnirad-500, Omnirad-2959, and Omnirad-127 (trade names, all manufactured by IGM Resins BV) can be used. As the aminoacetophenone compound, for example, commercially available products Omnirad-907, Omnirad-369, and Omnirad-379EG (trade names, all manufactured by IGM Resins BV) can be used. As the aminoacetophenone compound, compounds described in JP-A-2009-191179, which have an absorption wavelength matching a long-wavelength light source such as a wavelength of 365 nm or 405 nm, can also be used. As the acylphosphine compound, commercially available products Omnirad-819 and Omnirad-TPO (trade names, both manufactured by IGM Resins BV) can be used.
[0243] As the photopolymerization initiator, an oxime ester-based polymerization initiator (oxime compound) is more preferable. In particular, an oxime compound is preferable because it has high sensitivity and high polymerization efficiency, and it is easy to design the content of the coloring material in the composition to be high. Specific examples of the oxime compound that can be used include the compounds described in JP-A-2001-233842, JP-A-2000-80068, and JP-A-2006-342166. Examples of the oxime compound include 3-benzoyloxyiminobutan-2-one, 3-acetoxyiminobutan-2-one, 3-propionyloxyiminobutan-2-one, 2-acetoxyiminopentan-3-one, 2-acetoxyimino-1-phenylpropan-1-one, 2-benzoyloxyimino-1-phenylpropan-1-one, 3-(4-toluenesulfonyloxy)iminobutan-2-one, and 2-ethoxycarbonyloxyimino-1-phenylpropan-1-one. Further examples include the compounds described in J.C.S. Perkin II (1979) pp.1653-1660, J.C.S. Perkin II (1979) pp.156-162, Journal of Photopolymer Science and Technology (1995) pp.202-232, JP-A No. 2000-066385, JP-A No. 2000-080068, JP-T No. 2004-534797, and JP-A No. 2006-342166. Commercially available products include IRGACURE-OXE01 (manufactured by BASF), IRGACURE-OXE02 (manufactured by BASF), IRGACURE-OXE03 (manufactured by BASF), and IRGACURE-OXE04 (manufactured by BASF). In addition, TR-PBG-304 (manufactured by Changzhou Strong Electronic New Materials Co., Ltd.), Adeka Arcles NCI-831, Adeka Arcles NCI-930 (manufactured by ADEKA), and N-1919 (carbazole oxime ester skeleton-containing photoinitiator (manufactured by ADEKA)) can also be used.
[0244] In addition, as oxime compounds other than those described above, the compound described in JP-T-2009-519904 A in which an oxime is linked to the N-position of the carbazole; the compound described in U.S. Pat. No. 7,626,957 A in which a heterosubstituent is introduced at the benzophenone moiety; the compounds described in JP-A-2010-015025 A and U.S. Patent Publication No. 2009-292039 A in which a nitro group is introduced at the dye moiety; the ketoxime compounds described in WO-A-2009-131189; and the compound described in U.S. Pat. No. 7,556,910 which contains a triazine skeleton and an oxime skeleton in the same molecule; and the compound described in JP-A-2009-221114 A which has an absorption maximum at 405 nm and has good sensitivity to a g-line light source; etc. may be used. For example, see paragraphs 0274 to 0275 of JP 2013-029760 A, the contents of which are incorporated herein by reference. Specifically, the oxime compound is preferably a compound represented by the following formula (OX-1): The oxime compound may be an oxime compound in which the NO bond is an (E) form, an oxime compound in which the NO bond is an (Z) form, or a mixture of the (E) form and the (Z) form.
[0245] [ka]
[0246] In formula (OX-1), R and B each independently represent a monovalent substituent, A represents a divalent organic group, and Ar represents an aryl group. In formula (OX-1), the monovalent substituent represented by R is preferably a monovalent nonmetallic atomic group. Examples of the monovalent nonmetallic atomic group include an alkyl group, an aryl group, an acyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, a heterocyclic group, an alkylthiocarbonyl group, and an arylthiocarbonyl group. These groups may have one or more substituents. The aforementioned substituents may be further substituted with other substituents. Examples of the substituent include a halogen atom, an aryloxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an acyloxy group, an acyl group, an alkyl group, and an aryl group. In formula (OX-1), the monovalent substituent represented by B is preferably an aryl group, a heterocyclic group, an arylcarbonyl group, or a heterocyclic carbonyl group, and more preferably an aryl group or a heterocyclic group. These groups may have one or more substituents. Examples of the substituent include the above-mentioned substituents. In formula (OX-1), the divalent organic group represented by A is preferably an alkylene group, a cycloalkylene group, or an alkynylene group having 1 to 12 carbon atoms. These groups may have one or more substituents. Examples of the substituents include the above-mentioned substituents.
[0247] As the photopolymerization initiator, an oxime compound containing a fluorine atom can also be used. Specific examples of the oxime compound containing a fluorine atom include the compounds described in JP-A-2010-262028; compounds 24, 36 to 40 described in JP-T-2014-500852; and compound (C-3) described in JP-A-2013-164471. The contents of these compounds are incorporated herein by reference.
[0248] As the photopolymerization initiator, compounds represented by the following general formulas (1) to (4) can also be used.
[0249] [ka]
[0250] [ka]
[0251] In formula (1), R 1 and R 2 each independently represents an alkyl group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 4 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an arylalkyl group having 7 to 30 carbon atoms; R 1 and R 2 When R is a phenyl group, the phenyl groups may be bonded to each other to form a fluorene group, 3 and R 4 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms, and X represents a direct bond or a carbonyl group.
[0252] In formula (2), R 1 , R 2 , R 3 , and R 4 is R in formula (1). 1 , R 2 , R 3 , and R 4 is synonymous with R 5 -R 6, -OR 6 , -SR 6 , -COR 6 , -CONR 6 R 6 , -NR 6 COR 6 , -OCOR 6 , -COOR 6 , -SCOR 6 , -OCSR 6 , -COSR 6 , -CSOR 6 , -CN, a halogen atom, or a hydroxyl group; R 6 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms; X represents a direct bond or a carbonyl group; and a represents an integer of 0 to 4.
[0253] In formula (3), R 1 represents an alkyl group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 4 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an arylalkyl group having 7 to 30 carbon atoms; R 3 and R 4 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms, and X represents a direct bond or a carbonyl group.
[0254] In formula (4), R 1 , R 3 , and R 4 is R in Eq. (3). 1 , R 3 , and R 4 is synonymous with R 5 -R 6 , -OR 6 , -SR 6 , -COR 6 , -CONR 6 R 6 , -NR 6 COR 6 , -OCOR 6 , -COOR 6 , -SCOR 6 , -OCSR6 , -COSR 6 , -CSOR 6 , -CN, a halogen atom, or a hydroxyl group; R 6 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 30 carbon atoms, an arylalkyl group having 7 to 30 carbon atoms, or a heterocyclic group having 4 to 20 carbon atoms; X represents a direct bond or a carbonyl group; and a represents an integer of 0 to 4.
[0255] In the above formulas (1) and (2), R 1 and R 2 is preferably a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclohexyl group, or a phenyl group. 3 R is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a xylyl group. 4 R is preferably an alkyl group having 1 to 6 carbon atoms or a phenyl group. 5 is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a naphthyl group. X is preferably a direct bond. In addition, in the above formulas (3) and (4), R 1 is preferably a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclohexyl group, or a phenyl group. 3 R is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a xylyl group. 4 is preferably an alkyl group having 1 to 6 carbon atoms or a phenyl group. 5 is preferably a methyl group, an ethyl group, a phenyl group, a tolyl group, or a naphthyl group. X is preferably a direct bond. Specific examples of the compounds represented by formula (1) and formula (2) include the compounds described in paragraphs 0076 to 0079 of JP2014-137466A, the contents of which are incorporated herein by reference.
[0256] Specific examples of oxime compounds that can be preferably used in the above composition are shown below. Among the oxime compounds shown below, the oxime compound represented by the general formula (C-13) is more preferred. In addition, as the oxime compound, compounds described in Table 1 of International Publication No. 2015-036910 can also be used, the contents of which are incorporated herein by reference.
[0257] [ka]
[0258] [ka]
[0259] The oxime compound preferably has a maximum absorption wavelength in the wavelength region of 350 to 500 nm, more preferably has a maximum absorption wavelength in the wavelength region of 360 to 480 nm, and further preferably has high absorbance at wavelengths of 365 nm and 405 nm. The molar absorption coefficient of the oxime compound at 365 nm or 405 nm is preferably from 1,000 to 300,000, more preferably from 2,000 to 300,000, and even more preferably from 5,000 to 200,000, from the viewpoint of sensitivity. The molar absorption coefficient of a compound can be measured by a known method, but it is preferable to measure it, for example, using an ultraviolet-visible spectrophotometer (Varian Cary-5 spectrophotometer) using ethyl acetate at a concentration of 0.01 g / L. Two or more kinds of photopolymerization initiators may be used in combination, if necessary.
[0260] In addition, as the photopolymerization initiator, compounds described in paragraph 0052 of JP 2008-260927 A, paragraphs 0033 to 0037 of JP 2010-97210 A, and paragraph 0044 of JP 2015-068893 A can also be used, the contents of which are incorporated herein by reference. In addition, oxime initiators described in Korean Patent Publication No. 10-2016-0109444 can also be used.
[0261] [Polymerization inhibitor] The composition may also include a polymerization inhibitor. The polymerization inhibitor is not particularly limited, and known polymerization inhibitors can be used. Examples of the polymerization inhibitor include phenol-based polymerization inhibitors (e.g., p-methoxyphenol, 2,5-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-methylphenol, 4,4'-thiobis(3-methyl-6-t-butylphenol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 4-methoxynaphthol, etc.); hydroquinone-based polymerization inhibitors (e.g., hydroquinone, 2,6-di-tert-butylhydroquinone, etc.); quinone, etc.); quinone-based polymerization inhibitors (e.g., benzoquinone, etc.); free radical-based polymerization inhibitors (e.g., 2,2,6,6-tetramethylpiperidine 1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical, etc.); nitrobenzene-based polymerization inhibitors (e.g., nitrobenzene, 4-nitrotoluene, etc.); and phenothiazine-based polymerization inhibitors (e.g., phenothiazine, 2-methoxyphenothiazine, etc.); and the like. Among these, phenol-based polymerization inhibitors or free radical-based polymerization inhibitors are preferred.
[0262] The effect of the polymerization inhibitor is remarkable when it is used together with a resin containing a curable group. The content of the polymerization inhibitor in the composition is not particularly limited, but is preferably from 0.0001 to 0.5 mass %, more preferably from 0.0001 to 0.2 mass %, and even more preferably from 0.0001 to 0.05 mass %, based on the total mass of the composition. The content of the polymerization inhibitor is preferably from 0.0001 to 0.5 mass %, more preferably from 0.0001 to 0.2 mass %, and even more preferably from 0.0001 to 0.05 mass %, based on the total solid content of the composition. In addition, the ratio of the content of the polymerization inhibitor to the content of the polymerizable compound (particularly, a compound containing a group having an ethylenically unsaturated bond) in the composition (content of the polymerization inhibitor / content of the polymerizable compound (mass ratio)) is preferably more than 0.0005, more preferably 0.0006 to 0.02, and even more preferably 0.0006 to 0.005.
[0263] [Surfactant] The composition may contain a surfactant. The surfactant contributes to improving the coatability of the composition. When the composition contains a surfactant, the content of the surfactant is preferably from 0.001 to 2.0 mass %, more preferably from 0.005 to 0.5 mass %, and even more preferably from 0.01 to 0.1 mass %, relative to the total mass of the composition. The content of the surfactant is preferably from 0.001 to 2.0 mass %, more preferably from 0.005 to 0.5 mass %, and even more preferably from 0.01 to 0.1 mass %, based on the total solid content of the composition.
[0264] Examples of the surfactant include a fluorine-based surfactant, a nonionic surfactant, a cationic surfactant, an anionic surfactant, and a silicone-based surfactant.
[0265] For example, if the composition contains a fluorine-based surfactant, the liquid properties (particularly, fluidity) of the composition are improved. That is, when a film is formed using a composition containing a fluorine-based surfactant, the interfacial tension between the surface to be coated and the coating liquid is reduced, improving the wettability to the surface to be coated, and improving the coatability to the surface to be coated. Therefore, even if a thin film of about several μm is formed with a small amount of liquid, it is effective in that a film of uniform thickness with little thickness unevenness can be more suitably formed.
[0266] The fluorine content in the fluorosurfactant is preferably 3 to 40 mass%, more preferably 5 to 30 mass%, and even more preferably 7 to 25 mass%. A fluorosurfactant having a fluorine content within this range is effective in terms of uniformity of the coating film thickness and / or liquid saving properties, and also has good solubility in the composition.
[0267] Examples of fluorine-based surfactants include those described in paragraphs 0060 to 0064 of JP 2014-041318 A (corresponding paragraphs 0060 to 0064 of WO 2014 / 017669 A), those described in paragraphs 0117 to 0132 of JP 2011-132503 A, and those described in JP 2020-008634 A, the contents of which are incorporated herein by reference. Commercially available fluorine-based surfactants include, for example, Megafac F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-554, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F-563, F-568, F-575, F-780, EXP, MFS-330, R-41, and R- 41-LM, R-01, R-40, R-40-LM, R-43, RS-43, TF-1956, RS-90, R-94, RS-72-K, DS-21 (all manufactured by DIC Corporation), Fluorard FC430, FC431, FC171 (all manufactured by Sumitomo 3M Limited), Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, KH-40 (all manufactured by AGC Corporation), PolyFox Examples of such agents include PF636, PF656, PF6320, PF6520, and PF7002 (all manufactured by OMNOVA), and Ftergent 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, and 245F (all manufactured by NEOS Corporation). A block polymer can also be used as the fluorine-based surfactant, and specific examples include the compounds described in JP-A-2011-089090. Examples of silicone surfactants include KF-6000, KF-6001, KF-6002, KF-6003, and KF6007 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0268] From the standpoint of environmental regulations, the use of perfluoroalkylsulfonic acids and their salts, and perfluoroalkylcarboxylic acids and their salts may be restricted. When the content of the above compounds in the composition is reduced, the content of perfluoroalkylsulfonic acid (particularly perfluoroalkylsulfonic acid having a perfluoroalkyl group with 6 to 8 carbon atoms) and its salt, and perfluoroalkylcarboxylic acid (particularly perfluoroalkylcarboxylic acid having a perfluoroalkyl group with 6 to 8 carbon atoms) and its salt is preferably 0.01 to 1,000 ppb, more preferably 0.05 to 500 ppb, and even more preferably 0.1 to 300 ppb, based on the total solid content of the composition. The composition may be substantially free of perfluoroalkylsulfonic acid and its salt, and perfluoroalkylcarboxylic acid and its salt. For example, a compound that can be a substitute for perfluoroalkylsulfonic acid and its salt, and a compound that can be a substitute for perfluoroalkylcarboxylic acid and its salt may be used to make the composition substantially free of perfluoroalkylsulfonic acid and its salt, and perfluoroalkylcarboxylic acid and its salt. Examples of compounds that can be a substitute for regulated compounds include compounds that are excluded from the scope of regulation due to the difference in the number of carbon atoms in the perfluoroalkyl group. However, the above content does not prevent the use of perfluoroalkylsulfonic acid and its salt, and perfluoroalkylcarboxylic acid and its salt. The composition may contain perfluoroalkylsulfonic acid and its salt, and perfluoroalkylcarboxylic acid and its salt within the maximum allowable range.
[0269] 〔solvent〕 The composition may include a solvent. The solvent includes water and organic solvents, with organic solvents being preferred. From the viewpoint of coatability, the boiling point of the solvent is preferably from 100 to 400° C., more preferably from 150 to 300° C., and further preferably from 170 to 250° C. In this specification, the boiling point means the normal boiling point, unless otherwise specified.
[0270] Examples of the organic solvent include acetone, methyl ethyl ketone, cyclohexane, ethyl acetate, ethylene dichloride, tetrahydrofuran, toluene, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, acetylacetone, cyclohexanone, cyclopentanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol monoisopropyl ether, and ethylene glycol monobutyl ether acetate. acetate, 1,4-butanediol diacetate, 3-methoxypropanol, methoxymethoxyethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, 3-methoxypropyl acetate, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, ethyl acetate, butyl acetate, methyl lactate, N-methyl-2-pyrrolidone, and ethyl lactate, but are not limited thereto.
[0271] When the composition contains a solvent, the content thereof is preferably 1 to 25 mass%, more preferably 1 to 15 mass%, and even more preferably 1 mass% or more and less than 12 mass%, relative to the total mass of the composition, in terms of better effects of the present invention. It is also preferable that the composition is substantially free of a solvent. The term "substantially free of a solvent" means that the content of the solvent is less than 1% by mass relative to the total mass of the composition, and for example, is preferably 0% by mass or more and less than 1% by mass, more preferably 0 to 0.5% by mass, and even more preferably 0 to 0.1% by mass. The solid content concentration of the composition is preferably from 20 to 100% by mass, more preferably from 40 to 100% by mass, and further preferably from 75 to 100% by mass.
[0272] [Other optional ingredients] The composition may further contain other optional components other than the above-mentioned components. For example, magnetic particles other than the specific magnetic particles, sensitizers, co-sensitizers, crosslinking agents (curing agents), heat curing accelerators, plasticizers, diluents, sensitizers, and rubber components may be mentioned, and further, known additives such as adhesion promoters to the substrate surface and other auxiliaries (for example, defoamers, flame retardants, leveling agents, peeling accelerators, antioxidants, fragrances, surface tension adjusters, and chain transfer agents) may be added as necessary.
[0273] [An example of a preferred embodiment of the composition] An example of a suitable embodiment of the composition is a composition containing specific magnetic particles, a rheology control agent, and a curing component that is cured by light or heat. Among them, the composition is preferably a composition containing specific magnetic particles, a rheology control agent, and a polymerizable compound, and more preferably a composition containing specific magnetic particles, a rheology control agent, and a compound containing at least one of an epoxy group and an oxetanyl group. In addition, when the composition contains a curing component that is cured by light, the composition preferably further contains a photopolymerization initiator. When the composition contains a curing component that is cured by heat, the composition may further contain a thermal polymerization initiator. When the composition contains a compound that contains at least one of an epoxy group and an oxetanyl group, the composition may further contain a curing accelerator.
[0274] [Physical Properties of Composition] When the shear rate is 0.1 (1 / s), the viscosity of the composition at 23° C. is preferably 1 to 1,000,000 Pa·s, more preferably 10 to 50,000 Pa·s, and even more preferably 50 to 10,000 Pa·s, in view of superior sedimentation stability of the specific magnetic particles. When the shear rate is 1000 (1 / s), the viscosity of the composition at 23°C is preferably 100 Pa s or less, more preferably 50 Pa s or less, and even more preferably 10 Pa s or less, in terms of superior sedimentation stability of the specific magnetic particles. When the shear rate is 1000 (1 / s), the lower limit is preferably 0.001 Pa s or more. Here, the viscosity of the composition at 23°C can be obtained by measuring at 23°C using MCR-102 (manufactured by Anton Paar) while increasing the speed from 0.1 / s to 1000 / s.
[0275] [Method of producing the composition] The composition can be prepared by mixing the above-mentioned components by a known mixing method (for example, a mixing method using a stirrer, a homogenizer, a high-pressure emulsifier, a wet grinder, or a wet disperser). When preparing the composition of the present invention, each component may be mixed at once, or each component may be dissolved or dispersed in a solvent and then mixed successively. The order of addition and working conditions when mixing are not particularly limited. For example, when using multiple types of other resins, they may be mixed at once, or each type may be mixed in multiple batches.
[0276] [An example of a suitable form of the composition] An example of a suitable form of the composition of the present invention (composition A) is a composition (hereinafter also referred to as "composition B") that contains magnetic particles having an average particle size of 2 to 30 μm and an aspect ratio of less than 8, and that contains 70 to 90 mass % Fe atoms and has a diffraction peak having a half-width of 0.2 to 3° in a 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by X-ray diffraction method, and a rheology control agent.
[0277] [Magnetic particle-containing film] The magnetic particle-containing film of the present invention is formed using the above-mentioned composition of the present invention. The thickness of the magnetic particle-containing film is preferably from 1 to 10,000 μm, more preferably from 10 to 1,000 μm, and even more preferably from 15 to 800 μm, in terms of superior magnetic permeability. The magnetic particle-containing film is suitably used as an electronic component such as an antenna or inductor mounted on an electronic communication device or the like.
[0278] [Method for producing a magnetic particle-containing film] The magnetic particle-containing film of the present invention can be obtained, for example, by curing the above-mentioned composition. The method for producing the magnetic particle-containing film is not particularly limited, but preferably includes the following steps. ·Composition layer formation process ·Curing process
[0279] <Composition layer formation process> In the composition layer forming step, a composition layer (composition layer) is formed by applying the composition onto a substrate (support) etc. As the substrate, for example, a wiring board having an antenna part or an inductor part etc. can be used.
[0280] The composition can be applied to a substrate by a variety of coating methods, including slit coating, inkjet, spin coating, casting, roll coating, and screen printing. The thickness of the composition layer is preferably 1 to 10,000 μm, more preferably 10 to 1,000 μm, and even more preferably 15 to 800 μm. The composition layer applied to the substrate may be heated (prebaked), and the prebaking can be performed, for example, on a hot plate or in an oven at a temperature of 50 to 140° C. for 10 to 1,800 seconds. Prebaking is preferably performed when the composition contains a solvent.
[0281] <Curing process> The curing step is not particularly limited as long as it can cure the composition layer, and examples thereof include a heat treatment for heating the composition layer and an exposure treatment for irradiating the composition layer with actinic rays or radiation.
[0282] When the heat treatment is carried out, the heat treatment can be carried out continuously or batchwise using a heating means such as a hot plate, a convection oven (hot air circulation type dryer), or a high-frequency heater. The heating temperature in the heat treatment is preferably 120 to 260° C., more preferably 150 to 240° C. The heating time is not particularly limited, but is preferably 10 to 1800 seconds. The pre-baking in the composition layer forming step may also serve as the heat treatment in the curing step.
[0283] When exposure treatment is performed, the method of irradiating with actinic rays or radiation is not particularly limited, but it is preferable to irradiate through a photomask having openings in a pattern. The exposure is preferably carried out by irradiation with radiation. The radiation that can be used for exposure is preferably ultraviolet light such as g-rays, h-rays, or i-rays, and the light source is preferably a high-pressure mercury lamp. The irradiation intensity is 5 to 1500 mJ / cm. 2 is preferable, and 10 to 1000 mJ / cm 2 is more preferred. When the composition contains a thermal polymerization initiator, the composition layer may be heated in the exposure treatment. The heating temperature is not particularly limited, but is preferably 80 to 250° C. The heating time is not particularly limited, but is preferably 30 to 300 seconds. In addition, when the composition layer is heated in the exposure treatment, this may also serve as a post-heating step described later. In other words, when the composition layer is heated in the exposure treatment, the manufacturing method of the magnetic particle-containing film does not need to include a post-heating step.
[0284] <Developing process> When an exposure treatment is performed in the curing step, a development step may be further included. The development step is a step of developing the composition layer after exposure to form a magnetic particle-containing film. By this step, the composition layer in the portion not irradiated with light in the exposure treatment is dissolved, and only the photocured portion remains, thereby obtaining a patterned magnetic particle-containing film. The type of developer used in the development step is not particularly limited, but an alkaline developer that does not damage circuits and the like is preferable. The development temperature is, for example, 20 to 30°C. The developing time is, for example, 20 to 90 seconds. In recent years, in order to remove residues more effectively, the developing time may be 120 to 180 seconds. Furthermore, in order to further improve the removability of residues, the process of shaking off the developing solution every 60 seconds and supplying new developing solution may be repeated several times.
[0285] The alkaline developer is preferably an alkaline aqueous solution prepared by dissolving an alkaline compound in water to a concentration of 0.001 to 10% by mass (preferably 0.01 to 5% by mass). Examples of alkaline compounds include sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, aqueous ammonia, ethylamine, diethylamine, dimethylethanolamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxyl, benzyltrimethylammonium hydroxide, choline, pyrrole, piperidine, and 1,8-diazabicyclo[5.4.0]-7-undecene (among these, organic alkalis are preferred). When an alkaline developer is used, a washing treatment with water is generally carried out after development.
[0286] <Post bake> When an exposure treatment is performed in the curing step, it is preferable to perform a heat treatment (post-baking) after the curing step. Post-baking is a heat treatment for completing the curing. When a development step is performed, it is preferable to perform post-baking after the development step. The heating temperature is preferably 240° C. or less, more preferably 220° C. or less. There is no particular lower limit, but in consideration of efficient and effective processing, it is preferably 50° C. or more, more preferably 100° C. or more. In addition, the heating time is not particularly limited, but is preferably 10 to 1800 seconds. The post-baking can be carried out continuously or batchwise using a heating means such as a hot plate, a convection oven (hot air circulation dryer), or a high-frequency heater.
[0287] The post-baking is preferably carried out in an atmosphere with a low oxygen concentration. The oxygen concentration is preferably 19% by volume or less, more preferably 15% by volume or less, even more preferably 10% by volume or less, particularly preferably 7% by volume or less, and most preferably 3% by volume or less. There is no particular lower limit, but a concentration of 10 ppm by volume or more is practical.
[0288] Moreover, instead of the post-baking by heating, the curing may be completed by UV (ultraviolet) irradiation. In this case, the composition preferably further contains a UV curing agent. The UV curing agent is preferably a UV curing agent that can be cured at a wavelength shorter than 365 nm, which is the exposure wavelength of a polymerization initiator added for a lithography process using normal i-line exposure. An example of the UV curing agent is Chiba Ilgacure 2959 (trade name). In the case of performing UV irradiation, it is preferable that the composition layer is a material that cures at a wavelength of 340 nm or less. There is no particular lower limit of the wavelength, but it is generally 220 nm or more. The exposure dose of UV irradiation is preferably 100 to 5000 mJ, more preferably 300 to 4000 mJ, and even more preferably 800 to 3500 mJ. It is preferable to perform this UV curing process after the exposure treatment in order to perform low-temperature curing more effectively. It is preferable to use an ozone-free mercury lamp as the exposure light source.
[0289] [Electronic components] The electronic component of the present invention includes the above-mentioned magnetic particle-containing film of the present invention. That is, the electronic component of the present invention may include the above-mentioned magnetic particle-containing film as a part of the component. Examples of the electronic component include an inductor and an antenna. The electronic component may have a known structure. EXAMPLES
[0290] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples. In the following description, unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass".
[0291] [Various components used in the preparation of the composition] In preparing the composition, the components shown in Table 1 were prepared. The outline of each component shown in Table 1 is shown below.
[0292] [Magnetic particles] As the magnetic particles, P-1 to P-4 and CP-1 to CP-5 shown below were used. P-2 to P-4 and CP-1 to CP-2 were prepared by subjecting Fe-based amorphous to a predetermined heat treatment, and the aspect ratio was adjusted by mechanochemical treatment using a bead mill. P-1: Product name "KUAMET NC1" (manufactured by Epson Atmix) "Fe nanocrystalline alloy, crystalline (has a crystal structure derived from Fe), Fe atom content: 83% by mass, D50: 23 μm, aspect ratio: 1 to 2, solid content: 100% by mass" P-2: Fe nanocrystalline alloy “Crystalline (has a crystal structure derived from Fe), Fe atom content: 83 mass%, D50: 3 μm, aspect ratio: 1 to 2, solid content: 100 mass%” P-3: Fe nanocrystalline alloy “Crystalline (has a crystal structure derived from Fe), Fe atom content: 83 mass%, D50: 30 μm, aspect ratio: 1 to 2, solid content: 100 mass%” P-4: Fe nanocrystalline alloy "Crystalline (has a crystal structure derived from Fe), Fe atom content: 83 mass%, D50: 28 μm, aspect ratio: 7 or more but less than 8, solid content: 100 mass%"
[0293] CP-1: Fe nanocrystalline alloy “Crystalline (has a crystal structure derived from Fe), Fe atom content: 83 mass%, D50: 35 μm, aspect ratio: 1 to 2, solid content: 100 mass%” CP-2: Fe nanocrystalline alloy “Crystalline (has a crystal structure derived from Fe), Fe atom content: 83% by mass, D50: 28 μm, aspect ratio: 8-9, solid content: 100% by mass”
[0294] CP-3: Product name "AW2-08 PF-3F" (manufactured by Epson Atmix) "Fe-based amorphous, non-crystalline (does not have a crystal structure derived from Fe), Fe atom content: 87% by mass, D50: 3 μm, aspect ratio: 1 to 2, solid content: 100% by mass" CP-4: Product name "EA-SMP-10 PF-5F" (manufactured by Epson Atmix) "FeSiCr, crystalline (has a crystal structure derived from Fe), Fe atom content: 92% by mass, D50: 4 μm, aspect ratio: 1 to 2, solid content: 100% by mass" CP-5: Product name "JRM35G" (manufactured by Japan Metals and Chemical Industries Co., Ltd.) "Ni-Zn ferrite, crystalline (has a crystal structure derived from Fe), Fe atom content: <47% by mass, D50: 33 μm, aspect ratio: 1 to 2, solid content: 100% by mass"
[0295] [Rheology control agents and other resins] D-1: Product name "BYK-P105" (manufactured by BYK) "Polymer of low molecular weight unsaturated carboxylic acid, solid content: 100% by mass" D-2: Product name "ANTI-TERRA 204" (manufactured by BYK) "Polyaminoamide polycarboxylate solution, solids concentration: 52% by mass" D-3: Product name "Tallen VA705B" (Kyoeisha Chemical Co., Ltd.) "Higher fatty acid amide, solid content: 100% by mass" D-4: Product name: "FLOWNON RCM-230AF" (Kyoeisha Chemical Co., Ltd.) "Solution of higher fatty acid amide, solids concentration 10%" D-5: Phenylphosphonic acid (Nissan Chemicals) “100% solids”
[0296] D-1 and D-3 are the rheology control agents themselves, and D-2 and D-4 are solutions containing the rheology control agents (solid content). In addition, D-5 does not qualify as a rheology control agent.
[0297] [Polymerizable compound] M-1: Celloxide 2021P (manufactured by Daicel Chemical Industries, Ltd.) "3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, solid content concentration 100% by mass" M-2: Denacol EX-411 (Nagase ChemteX Corporation) "Pentaerythritol polyglycidyl ether, solids concentration: 100% by mass" M-3: KAYARAD RP-1040 (manufactured by Nippon Kayaku) "Compounds listed below, solid content concentration 100% by mass"
[0298] [ka]
[0299] M-4: A-TMMT (manufactured by Toagosei Co., Ltd.), "Pentaerythritol tetraacrylate, solid content concentration 100% by mass"
[0300] [Additives] A-1: Triphenylphosphine (Tokyo Chemical Industry Co., Ltd.) "Solid content: 100% by mass, hardening accelerator" A-2: Hishicoline PX-4MP (manufactured by Nippon Chemical Industry Co., Ltd.) "Solid content: 100% by mass, methyl tributyl phosphonium dimethyl phosphate, hardening accelerator" A-3: IRGACURE-OXE03 (BASF) "Solid content: 100% by mass, oxime ester photopolymerization initiator" A-4: Omnirad-369 (IGM Resins BV) "Solid content: 100% by mass, α-aminoalkylphenone photopolymerization initiator" Sur-1: MEGAFAC F-781F (DIC Corporation) "Solid content: 100% by weight, fluorosurfactant" Sur-2: KF-6001 (Shin-Etsu Chemical Co., Ltd.) "Solid content: 100% by mass, silicone surfactant, polydimethylsiloxane modified with carbinol at both ends"
[0301] 〔solvent〕 S-1: Propylene glycol monomethyl ether acetate (PGMEA) (Tokyo Chemical Industry Co., Ltd.) S-2: 1,4-butanediol diacetate (1,4-BDDA) (manufactured by Daicel Chemical Industries, Ltd.)
[0302] [Preparation of compositions of examples and comparative examples] The components other than the solvent shown in Table 1 were mixed in the composition ratio (mass basis) shown in Table 1 and placed in a sealed container made of PTFE (polytetrafluoroethylene). Next, a solvent was added to the composition ratio (mass basis) shown in Table 1, and the container was sealed. The mixture was dispersed at 50 G for 2 hours using a RAM (low frequency resonant acoustic mixer) manufactured by Resodyn, to prepare the compositions of each of the examples and comparative examples.
[0303] [evaluation] [Magnetic permeability] Using an applicator, each composition of the Examples and Comparative Examples was applied onto a Si wafer having a thickness of 100 μm so that the film thickness after formation was 100 μm, thereby forming a coating film. Next, when the applied composition did not contain a photopolymerization initiator, the resulting coating was heated and dried at 100°C for 10 minutes, and then heated at 230°C for 10 minutes to produce a substrate with a cured film. When the applied composition contained a photopolymerization initiator, the coating was heated and dried at 1000 mJ / cm2 using a proximity exposure machine. 2 The exposure treatment was carried out under the above conditions, and then heating was carried out at 230° C. for 10 minutes to prepare a substrate with a cured film. Next, the obtained substrate with the cured film was cut into a size of 1 cm x 2.8 cm together with the substrate to prepare a sample substrate for measurement. Thereafter, the magnetic permeability at 50 MHz of the cured film on each of the obtained measurement sample substrates was measured using PER-01 (a high frequency magnetic permeability measuring device manufactured by Keycom Corporation) to obtain the relative magnetic permeability μ′ of the film. The obtained relative magnetic permeability μ′ was evaluated according to the following evaluation criteria. In practice, an evaluation of “B” or higher is preferable. (Evaluation Criteria) "A": 10≦μ' "B": 5≦μ'<10 「C」: μ'<5
[0304] [Acid resistance] The measurement sample substrate prepared in the above-mentioned magnetic permeability evaluation was immersed in 10% HCl aq. for 30 minutes, and then the magnetic permeability of the cured film on the substrate at 50 MHz was measured using PER-01 (Keycom Corporation, high frequency magnetic permeability measuring device) to obtain the relative magnetic permeability μ' of the film. Next, the rate of change Δμ′ (%) before and after immersion was calculated using the following formula (1). Rate of change Δμ'(%)={|Relative magnetic permeability μ' after immersion - Relative magnetic permeability μ' before immersion | / Relative magnetic permeability μ' before immersion}×100 The obtained value of the rate of change Δμ′ was evaluated according to the following evaluation criteria. In practice, an evaluation of “B” or higher is preferable. (Evaluation Criteria) "A": Δμ'<3% "B": 3%≦Δμ'<10% "C": 10%≦Δμ'
[0305] [Sedimentation stability] 3 mL of each composition of the Examples and Comparative Examples was placed in a transparent glass container (cylindrical, diameter 23 mm×height 35 mm), sealed, and allowed to stand at 25° C. for one month. Thereafter, the composition in the glass container was visually observed, and the distance d1 from the gas-liquid interface to the interface between the transparent region and the opaque region, and the distance d2 from the gas-liquid interface to the bottom surface of the glass container were measured. Next, the same glass container was stirred at 3300 rpm / min for 30 seconds using a shaker Se-08 manufactured by Taitec Corporation, and then allowed to stand for 12 hours at 25° C. Thereafter, the composition in the glass container was visually observed, and the distance d1′ from the gas-liquid interface to the interface between the transparent region and the opaque region, and the distance d2′ from the gas-liquid interface to the bottom surface of the glass container were measured. The sedimentation stability was evaluated according to the following criteria using the distances d1 and d2, and the distances d1' and d2'. If the following criteria were "B" or higher, it was determined that the sedimentation stability was excellent. The results are shown in Table 1. (Evaluation Criteria) "A": 0≦d1 / d2≦0.1 and 0≦d1' / d2'≦0.1 (liquid does not completely separate over time) "B": 0.1 < d1 / d2 ≤ 0.3 and 0 ≤ d1' / d2' ≤ 0.1 (The liquid separates slightly over time but returns with stirring) "C": 0.3 < d1 / d2 or 0.1 < d1' / d2' (The liquid separates over time and does not return even with stirring)
[0306] 〔Coating Applicability〕 The coating applicability was evaluated based on whether coating using an applicator in the magnetic permeability evaluation was possible. Specifically, the evaluation was carried out according to the following evaluation criteria. "A": Coatable "B": The fluidity of the composition is poor, but it is coatable "C": The fluidity of the composition is poor and it is uncoatable
[0307] Table 1 below shows the formulation of each composition and the results of the evaluation tests conducted on each composition. In the following evaluation, the "half-value width of the X-ray diffraction peak" means the half-value width (°) of the diffraction peak that appears in the range of 2θ = 42 - 48° in the X-ray diffraction pattern obtained by the X-ray diffraction method. The X-ray diffraction measurement of the specific magnetic particles was carried out in the powder state based on the following apparatus and conditions. Apparatus name: X'Pert PRO MPD (manufactured by PANalytical) Measurement conditions: Using a Cu line source (output: 45 kV, 40 mA) Scan conditions: The range of 20 - 70° at 0.053° / step, 0.71° / min
[0308]
Table 1
[0309] From the results in Table 1, it is clear that the compositions of the examples can form magnetic particle-containing films with excellent magnetic permeability and acid resistance. Also, it is clear that the compositions of the examples are excellent in sedimentation stability. Furthermore, a comparison of Examples 1 to 4 confirmed that when the average particle size (D50) of the specific magnetic particles was 28 μm or less, the sedimentation stability of the composition was superior. Furthermore, a comparison of Examples 1 to 4 confirmed that when the aspect ratio of the specific magnetic particles is less than 7, the sedimentation stability of the composition is superior. Furthermore, by comparing Examples 1, 6, and 7, it was confirmed that when the content of the specific magnetic particles is 75 mass% or more relative to the total mass of the composition, the magnetic permeability of the magnetic particle-containing film formed is superior. Furthermore, by comparing Examples 1, 6, and 7, it was confirmed that the coating suitability of the composition was superior when the content of the specific magnetic particles was 85 mass % or less relative to the total mass of the composition. Furthermore, a comparison between Examples 1, 19, and 20 confirmed that when the content of the solvent in the composition was less than 12 mass %, the sedimentation stability of the composition was superior.
[0310] On the other hand, the compositions of the comparative examples did not provide the desired effects.
Claims
1. magnetic particles containing 70 to 90% by mass of Fe atoms, having a crystal structure of Fe, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; A rheology control agent; A polymerizable compound, A composition comprising:
2. The composition according to claim 1 , wherein the rheology control agent is at least one selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes.
3. The composition according to claim 1 or 2, wherein the polymerizable compound comprises a compound containing one or more of an epoxy group and an oxetanyl group.
4. A magnetic particle containing 70 to 90 mass % Fe atoms, having an Fe crystal structure, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; A rheology control agent; A polymerizable compound, The composition, wherein the rheology control agent is at least one selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes.
5. The composition of claim 4, wherein the polymerizable compound comprises a compound containing one or more of an epoxy group and an oxetanyl group.
6. A magnetic particle containing 70 to 90 mass % Fe atoms, having an Fe crystal structure, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; A rheology control agent; a polymerizable compound having a polymerizable group selected from the group consisting of an ethylenically unsaturated group, an epoxy group, and an oxetanyl group, The content of the polymerizable compound is 3 to 27% by mass based on the total solid content of the composition.
7. The composition described in claim 6, wherein the rheology control agent is one or more selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes.
8. The composition described in any one of claims 4 to 7, further comprising a polymerization initiator.
9. The composition according to any one of claims 1 to 8, wherein the magnetic particles have a half-value width of a diffraction peak appearing in a 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by an X-ray diffraction method of 0.2 to 3°.
10. magnetic particles containing 70 to 90 mass % Fe atoms, having a half-width of a diffraction peak appearing in a 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by an X-ray diffraction method of 0.2 to 3°, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; A rheology control agent; A polymerizable compound, A composition comprising:
11. The composition according to claim 10, wherein the rheology control agent is one or more selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes.
12. The composition according to claim 10 or 11, wherein the polymerizable compound comprises a compound containing one or more of an epoxy group and an oxetanyl group.
13. Magnetic particles containing 70 to 90 mass % Fe atoms, having a half-width of a diffraction peak appearing in a 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by an X-ray diffraction method of 0.2 to 3°, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; A rheology control agent; A polymerizable compound, The composition, wherein the rheology control agent is at least one selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes.
14. The composition of claim 13, wherein the polymerizable compound comprises a compound containing one or more of an epoxy group and an oxetanyl group.
15. Magnetic particles containing 70 to 90 mass % Fe atoms, having a half-width of a diffraction peak appearing in a 2θ range of 42 to 48° in an X-ray diffraction pattern obtained by an X-ray diffraction method of 0.2 to 3°, an average particle size of 2 to 30 μm, and an aspect ratio of less than 8; A rheology control agent; a polymerizable compound having a polymerizable group selected from the group consisting of an ethylenically unsaturated group, an epoxy group, and an oxetanyl group, The content of the polymerizable compound is 3 to 27% by mass based on the total solid content of the composition.
16. The composition described in claim 15, wherein the rheology control agent is one or more selected from the group consisting of polycarboxylic acids, polycarboxylic anhydrides, and amide waxes.
17. The composition described in any one of claims 13 to 16, further comprising a polymerization initiator.
18. The composition according to any one of claims 1 to 17, wherein the content of the magnetic particles is 70 to 90% by mass, based on the total mass of the composition.
19. the composition is substantially free of solvent; or The composition according to any one of claims 1 to 18, further comprising a solvent, and the content of the solvent is 1 mass% or more and less than 12 mass% with respect to the total mass of the composition.
20. A magnetic particle-containing film formed using the composition according to any one of claims 1 to 19.
21. An electronic component comprising the magnetic particle-containing film according to claim 20.
22. 22. The electronic component of claim 21 used as an inductor.
23. 22. The electronic component according to claim 21, used as an antenna.
Citation Information
Patent Citations
Magnetic-sheet manufacturing method
JP2008251735A
Method for manufacturing magnetic composite material, and compact
JP2009155545A
Magnetic sheet and antenna device comprising the same
JP2018029169A
Method for manufacturing inductor substrate
JP2019067960A